Optical laminate and image display device
Patent Information
- Application Number
- CN202610481861.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-15
- Filing Date
- 2026-04-13
- Publication Date
- 2026-10-23
AI Technical Summary
[0029]根据本发明,提供在偏振片的偏振度存在一定程度的面内偏差的情况下,从斜向观看时的外部光反射特性优异的光学层叠体等。
Smart Images

Figure CN122962708A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to optical laminates and image display devices. Background Technology
[0002] Previously, as a circular polarizing plate that improves oblique visibility, there are known optical laminates with λ / 2 and λ / 4 sections arranged at an axial angle of 60°.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-137939 Summary of the Invention
[0006] The problem that the invention aims to solve
[0007] However, even with a certain degree of in-plane deviation in the polarization degree of the polarizer, there is still room for improvement in the external light reflection characteristics when viewed from an oblique angle.
[0008] The present invention was made in view of the above-mentioned problems, and its object is to provide an optical laminate with excellent external light reflection characteristics when viewed from an oblique angle, even when there is a certain degree of in-plane deviation in the polarization degree of the polarizer.
[0009] Methods for solving problems
[0010] [1] An optical laminate comprising a linear polarizer and a phase difference layer laminate.
[0011] The in-plane standard deviation σ of the visibility correction polarization degree of the above-mentioned linear polarizer is greater than 0.001%.
[0012] The aforementioned phase difference layer stack has λ / 2 and λ / 4 portions sequentially from the side closest to the linear polarizer.
[0013] The aforementioned λ / 2 portion has one pair of in-phase retardation layers and at least one thickness-direction retardation layer disposed between the pair of in-phase retardation layers.
[0014] The aforementioned λ / 4 section has at least one thickness-direction phase retardation layer and at least one in-plane phase retardation layer sequentially from the side closest to the aforementioned linear polarizer.
[0015] [2] According to the optical laminate described in [1], the above-mentioned linear polarizer is a cured product of dichroic pigment and polymeric liquid crystal compound oriented.
[0016] [3] According to the optical laminate described in [1] or [2], wherein the indentation elastic modulus of the above-mentioned linear polarizer is 10000 MPa or less.
[0017] [4] The optical laminate described in any one of [1] to [3], wherein the Nz coefficient at a wavelength of 550 nm of the above-mentioned λ / 2 portion is 0.6 or more and less than 1.0.
[0018] [5] According to any one of [1] to [4], the optical laminate, when viewed from the thickness direction of the optical laminate, has an angle of 5° or less between the slow axes of the two phase difference layers in the λ / 2 portion.
[0019] [6] An optical laminate according to any one of [1] to [5], wherein, in the above-mentioned λ / 2 part, the sum of the thickness direction phase differences at 550 nm of the at least one thickness direction phase difference layer is -90 nm to -40 nm.
[0020] [7] An optical laminate according to any one of [1] to [6], wherein in the above-mentioned λ / 2 part, the number of the at least one phase difference layer in the thickness direction is 1.
[0021] [8] An optical laminate according to any one of [1] to [7], wherein, in the above-mentioned λ / 4 part, the sum of the thickness direction phase differences at 550 nm of the at least one thickness direction phase difference layer is -120 nm or more.
[0022] [9] According to any one of [1] to [8], the optical laminate, when viewed from the thickness direction of the optical laminate, has an angle of approximately 15° between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion, and an angle of approximately 75° between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion, or the angle of approximately 75° between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion, and an angle of approximately 15° between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion.
[0023]
[10] An optical laminate according to any one of [1] to [9], wherein the in-plane phase difference layers of the above-mentioned λ / 2 portion and the above-mentioned λ / 4 portion are polymers of polymeric liquid crystal compounds oriented and are reverse wavelength dispersive λ / 4 plates.
[0024]
[11] According to any one of [1] to
[10] , the thickness direction phase difference layers of the above-mentioned λ / 2 part and the above-mentioned λ / 4 part are polymers of polymeric liquid crystal compounds oriented and are positive C plates.
[0025]
[12] An optical laminate according to any one of [1] to
[11] , wherein, in the aforementioned phase difference layer laminate, at least one of the aforementioned in-plane phase difference layers is laminated with any of the aforementioned thickness direction phase difference layers without passing through an adhesive layer.
[0026]
[13] The optical laminate described in any one of [1] to
[12] further comprises one or more bonding layers, wherein the bonding layer is a cured layer of an ultraviolet-curable adhesive.
[0027]
[14] An image display device comprising a reflective image display layer and an optical laminate as described in any one of [1] to
[13] .
[0028] Invention Effects
[0029] According to the present invention, an optical laminate with excellent external light reflection characteristics when viewed from an oblique angle is provided, even when the polarization degree of the polarizer has a certain degree of in-plane deviation. Attached Figure Description
[0030] Figure 1 This is a cross-sectional view of an optical laminate (circular polarizer) according to one embodiment.
[0031] Figure 2 This is a cross-sectional view of an optical laminate (circular polarizer) according to one embodiment.
[0032] Figure 3 This is an example of a diagram showing the relationship between the transmission axis 120TA of a linear polarizer in an optical laminate and the slow axis 300SA of the λ / 2 portion and the slow axis 400SA of the λ / 4 portion.
[0033] Figure 4 This is another example of a diagram showing the relationship between the transmission axis 120TA of a linear polarizer in an optical laminate and the slow axis 300SA of the λ / 2 portion and the slow axis 400SA of the λ / 4 portion.
[0034] Explanation of reference numerals in the attached figures
[0035] 1…image display device, 10…optical laminate, 120…linear polarizer, 300…λ / 2 part, 310…in-plane phase difference layer (phase difference layer), 320…thickness direction phase difference layer (phase difference layer), 400…λ / 4 part, 420…thickness direction phase difference layer, 600…phase difference layer laminate. Detailed Implementation
[0036] Hereinafter, embodiments of the present invention will be described. First, the terminology used in this disclosure will be explained.
[0037] [Phase difference layer]
[0038] In this disclosure, the phase difference layer refers to an optical medium with birefringence. Birefringence refers to the different optical properties resulting from a difference in refractive index greater than 0.02 in at least two of three orthogonal directions.
[0039] [Refractive index of the phase retardation layer]
[0040] The refractive indices in the three orthogonal directions mentioned above in the retardation layer are referred to as nx, ny, and nz. nx represents the principal refractive index in the direction parallel to the plane of the retardation layer within the refractive index ellipsoid formed by the retardation layer. ny represents the refractive index in the direction parallel to the plane of the retardation layer and orthogonal to the nx direction within the refractive index ellipsoid formed by the retardation layer. nz represents the refractive index in the direction perpendicular to the plane of the retardation layer within the refractive index ellipsoid formed by the retardation layer.
[0041] [In-plane retardation and thickness-direction retardation of the phasing layer]
[0042] Delay is a physical quantity that represents the anisotropy of a phase difference layer. There are in-plane delay Re and thickness-direction delay Rth.
[0043] The in-plane delay Re(λ) at wavelength λnm is represented by equation (1). In equation (1), d represents the thickness (nm) of the phase difference layer.
[0044] Re(λ)=(nx-ny)×d…(1)
[0045] The thickness directional delay Rth(λ) at wavelength λnm is represented by equation (2). In equation (2), d is the same as d in equation (1) as the thickness (nm) of the phase difference layer.
[0046] Rth(λ)=-{nz-(nx+ny) / 2}×d…(2)
[0047] [Phase difference layer stack]
[0048] Optical stacks with multiple phase difference layers are sometimes referred to as phase difference layer stacks.
[0049] Next, embodiments of the present invention will be described with reference to the accompanying drawings. In the drawings, the same or equivalent parts are labeled with the same symbols, and repeated descriptions are omitted. The scale of the drawings may not be consistent with the scale of the description.
[0050] (Optical laminate (circular polarizer) 10)
[0051] like Figure 1 and Figure 2 As shown, the optical laminate 10 of the embodiment sequentially includes a polarizing plate 100, an adhesive layer D (200), a phase difference layer laminate 600, and an adhesive layer Z (700). It should be noted that the adhesive layer D (200) and the adhesive layer Z (700) are arbitrary components.
[0052] (Polarizing plate 100)
[0053] The polarizer 100 has a first protective layer 110, a linear polarizer 120, and a second protective layer 130 sequentially from the side opposite to the phase difference layer stack. It should be noted that the first protective layer 110 and the second protective layer 130 are arbitrary components.
[0054] (Linear polarizer 120)
[0055] The linear polarizer 120 has the function of selectively transmitting linearly polarized light in a certain direction from unpolarized light such as natural light. Examples of linear polarizers include: films formed by uniaxial stretching of a polymer such as PVA with iodine or organic dichroic dye impregnated in it (hereinafter also referred to as "polarizers"); and optically anisotropic layers formed by orienting dichroic dyes and polymeric liquid crystal compounds (hereinafter also referred to as "polarizing films").
[0056] The polarization performance of a linear polarizer can be measured using a spectrophotometer. For example, in the visible light range (380 nm to 780 nm), a spectrophotometer equipped with a prism polarizer can be used to measure the transmittance (T1) along the transmission axis (orientation perpendicular direction) and the transmittance (T2) along the absorption axis (orientation direction) using the two-beam method. Regarding the polarization performance in the visible light range, the single-unit transmittance and degree of polarization at each wavelength are calculated using the following equations (Equation 1) and (Equation 2). Visibility correction is then performed using the 2-degree field of view (C-light source) of the JIS Z8701, thereby allowing the calculation of the single-unit transmittance Ty and the degree of polarization Py corrected for visibility. Furthermore, based on the similarly measured transmittance, L is calculated using the color matching function of the C-light source. * a * b * (CIE) Colorimetric a in the color system * and b * This allows us to obtain the hue of a single linear polarizer (single hue), the hue of linear polarizers arranged in parallel (parallel hue), and the hue of linear polarizers arranged orthogonally (orthogonal hue). * and b * The closer the value is to 0, the more neutral the hue can be.
[0057] Monomer transmittance (%) = (T1 + T2) / 2 … (Equation 1)
[0058] Degree of polarization (%) = (T1-T2) / (T1+T2)×100 … (Equation 2)
[0059] It should be noted that, regarding the degree of polarization, the same measurement can be performed on a laminate with a protective layer or the like on the linear polarizer, as described in the embodiments below, and the obtained degree of polarization can be used as the degree of polarization of the linear polarizer. Specifically, if the linear polarizer does not contain a layer having an in-plane phase difference on at least one side, the degree of polarization of the linear polarizer can be measured by setting the incident surface during measurement to at least one of the aforementioned surfaces.
[0060] The visibility-corrected polarization degree Py of a linear polarizer is typically 80% or higher, preferably 90% or higher, more preferably 95% or higher, even more preferably 98% or higher, particularly preferably 99% or higher, and if it is 99.9% or higher, it can be suitable for use in liquid crystal displays. Increasing the visibility-corrected polarization degree Py of the linear polarizer is advantageous in improving the anti-reflective function of the optical laminate. If the visibility-corrected polarization degree Py is less than 80%, it may sometimes fail to perform its anti-reflective function when used as an anti-reflective film.
[0061] In this embodiment, the in-plane standard deviation σ of the visibility-corrected polarization degree Py of the linear polarizer is greater than 0.001%. This standard deviation σ can be 0.002% or more, 0.003% or more, 0.01% or more, 0.02% or more, 0.03% or more, 0.04% or more, 0.05% or more, or 0.06% or more. If this standard deviation σ is less than 0.001%, the linear polarizer has high orientation, and therefore, even when used as a circular polarizer stacked with any phase difference layer, the external light reflection characteristics when viewed from an oblique angle are not easily reduced. Furthermore, the standard deviation σ is typically 0.100% or less. If the standard deviation σ is too large, image display will become disordered when used in an image display device. The unit of the visibility-corrected polarization degree Py used in the calculation of the standard deviation σ is %.
[0062] The standard deviation is calculated based on measurement data at five points in the plane that are at least 5 cm apart. Specifically, it can be calculated using the method described in the examples below.
[0063] A higher transmittance Ty of the visibility-correcting monomer in a linear polarizer increases the clarity of white displays. However, as shown in Equations (1) and (2), excessively increasing the transmittance can lead to a decrease in polarization degree. Therefore, a transmittance of 30% or more and 60% or less is preferred, more preferably 35% or more and 55% or less, further preferably 38% or more and 50% or less, even more preferably 40% or more and 48% or less, even more preferably 41% or more and 47% or less, and particularly preferably 41.5% or more and 46% or less. If the transmittance Ty of the visibility-correcting monomer is too high, the polarization degree Py becomes too low, sometimes resulting in insufficient anti-reflective function when used as an anti-reflective film.
[0064] <Polarizer>
[0065] A film obtained by uniaxially stretching a polymer such as a polyvinyl alcohol (PVA) film while impregnating it with iodine or an organic dichroic dye can typically be manufactured through the following steps: uniaxial stretching of the PVA film; dyeing the PVA film with a dichroic dye such as iodine to adsorb the dye; treating the PVA film with the adsorbed dichroic dye using a crosslinking agent such as a boric acid aqueous solution; and washing with water after treatment with a crosslinking agent such as a boric acid aqueous solution. The polarizer may contain a crosslinking agent.
[0066] The thickness of the polarizer is typically 30 μm or less, preferably 18 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. This thickness is typically 1 μm or more, for example, 5 μm or more.
[0067] Uniaxial stretching of polyvinyl alcohol (PVA)-based resin films can be performed before, simultaneously with, or after dyeing with dichroic pigments. When uniaxial stretching is performed after dyeing, it can be done before or during boric acid treatment. Of course, uniaxial stretching can also be performed in multiple stages as shown here. Uniaxial stretching can be performed by: stretching uniaxially along the film transport direction between rollers with different circumferential speeds; stretching uniaxially along the film transport direction using heated rollers; stretching along the width direction using a tenter frame, etc. Furthermore, uniaxial stretching can be performed by dry stretching in the atmosphere or by wet stretching while the PVA-based resin film is swollen using a solvent such as water. The stretching ratio is typically around 3 to 8 times. Alternatively, an aqueous solution containing PVA can be coated onto a thermoplastic resin film, dried, and then stretched together with the thermoplastic resin film using the methods described above.
[0068] The dyeing of polyvinyl alcohol (PVA) resin films using dichroic pigments can be performed, for example, by immersing the PVA resin film in an aqueous solution containing a dichroic pigment. Specifically, iodine or dichroic organic dyes can be used as dichroic pigments. It should be noted that the PVA resin film is preferably pre-treated by immersion in water to induce swelling before dyeing.
[0069] When using iodine as a dichroic dye, the dyeing method typically involves impregnating a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide. The iodine content in this aqueous solution is typically approximately 0.01 to 1 part by weight relative to 100 parts by weight of water, and the potassium iodide content is typically approximately 0.5 to 20 parts by weight relative to 100 parts by weight of water. The temperature of the aqueous solution used for dyeing is typically around 20 to 40°C. Furthermore, the impregnation time (dyeing time) in this aqueous solution is typically around 20 to 1,800 seconds.
[0070] On the other hand, when using dichroic organic dyes as dichroic pigments, a common dyeing method involves impregnating a polyvinyl alcohol-based resin film in an aqueous solution containing the water-soluble dichroic organic dye. The content of the dichroic organic dye in this aqueous solution is typically about 0.0001 to 10 parts by weight relative to 100 parts by weight of water, preferably 0.001 to 1 part by weight. This dye aqueous solution may contain inorganic salts such as sodium sulfate as dyeing auxiliaries. The temperature of the dichroic organic dye aqueous solution used in dyeing is typically about 20 to 80°C. Furthermore, the impregnation time (dyeing time) in this aqueous solution is typically about 10 to 1,800 seconds.
[0071] Boric acid treatment following dyeing with a dichroic pigment can be carried out by immersing the dyed polyvinyl alcohol-based resin film in an aqueous solution containing boric acid. The boric acid content in the aqueous solution is typically about 2 to 15 parts by weight relative to 100 parts by weight of water, preferably 5 to 12 parts by weight. When iodine is used as the dichroic pigment, the aqueous solution containing boric acid preferably contains potassium iodide. The potassium iodide content in the aqueous solution is typically about 0.1 to 15 parts by weight relative to 100 parts by weight of water, preferably 5 to 12 parts by weight. The immersion time in the aqueous solution containing boric acid is typically about 60 to 1,200 seconds, preferably 150 to 600 seconds, and more preferably 200 to 400 seconds. The temperature of the aqueous solution containing boric acid is typically above 50°C, preferably 50 to 85°C, and more preferably 60 to 80°C.
[0072] Boric acid-treated polyvinyl alcohol (PVA) resin membranes are typically subjected to a water washing process. This washing can be performed, for example, by immersing the boric acid-treated PVA resin membrane in water. The water temperature during the washing process is typically around 5–40°C. Furthermore, the immersion time is typically around 1–120 seconds.
[0073] After washing, a drying process is performed to obtain a polarizing film. The drying process can be carried out using a hot air dryer or a far-infrared heater. The drying temperature is typically around 30–100°C, preferably 50–80°C. The drying time is typically around 60–600 seconds, preferably 120–600 seconds. Through the drying process, the moisture content of the polarizing film is reduced to a practical level. Its moisture content relative to the total mass of the polarizing film is typically around 5–20% by mass, preferably 8–15% by mass. If the moisture content is above 5% by mass, the polarizing film has sufficient flexibility, thus preventing damage or breakage after drying. Furthermore, if the moisture content is below 20% by mass, the polarizing film has sufficient thermal stability.
[0074] As described above, it is possible to manufacture polarizers formed by the adsorption and orientation of dichroic pigments on polyvinyl alcohol-based resin films.
[0075] <Polarizing film>
[0076] From the perspectives of being able to arbitrarily control hue, being able to achieve significant thinning, and having non-shrinkage properties due to the absence of thermal stretching relaxation, polarizing films, which are optical anisotropic layers of polymers containing dichroic pigments and polymeric liquid crystal compounds, can be suitable for applications such as flexible displays.
[0077] A polarizing film is formed by coating a polarizing film forming composition onto an alignment film formed on a substrate as needed, thereby orienting the dichroic pigments contained in the polarizing film forming composition. The polarizing film has a thickness of 0.1 μm or more and 5 μm or less, more preferably 0.3 μm or more and 4 μm or less, and even more preferably 0.5 μm or more and 3 μm or less. If the film thickness is thinner than this range, the desired light absorption may not be obtained, and if the film thickness is thicker than this range, there is a tendency for orientation defects to easily occur due to the reduced orientation constraint force of the alignment film. Furthermore, the polarizing film forming composition may further include solvents, photopolymerization initiators, photosensitizers, polymerization inhibitors, leveling agents, and adhesion enhancers.
[0078] For an optically anisotropic layer in which the dichroic pigment and polymeric liquid crystal compound are horizontally aligned with respect to the substrate surface, the ratio (dichroic ratio) of the absorbance A1(λ) in the orientation direction for light with wavelength λnm to the absorbance A2(λ) in the direction perpendicular to the orientation plane is preferably 7 or more, more preferably 20 or more, and even more preferably 40 or more. The higher this value, the better the absorption selectivity of the polarizer. Although it also depends on the type of dichroic pigment, in the case of a liquid crystal cured film cured in the state of a nematic liquid crystal phase, it is about 5 to 10.
[0079] By mixing two or more dichroic pigments with different absorption wavelengths, polarizing films of various hues can be produced, including polarizing films that absorb across the entire visible light spectrum. By creating polarizing films with such absorption characteristics, they can be applied to a wide range of applications.
[0080] <Polarizing films; polymeric liquid crystal compounds>
[0081] Polymerizable liquid crystal compounds refer to compounds that possess polymerizable groups and liquid crystal properties (hereinafter also referred to as polymerizable liquid crystals). Polymerizable groups are groups that participate in polymerization reactions, preferably photopolymerizable groups. Here, photopolymerizable groups refer to groups that can participate in polymerization reactions through active free radicals, acids, etc., generated by a photopolymerization initiator described later. Examples of polymerizable groups include: vinyl, ethoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, ethylene oxide, oxetyl, etc. Among these, acryloyloxy, methacryloyloxy, ethoxy, and oxetyl are preferred, and methacryloyloxy or acryloyloxy are more preferred. The liquid crystal property can be thermotropic liquid crystal or lyotropic liquid crystal; when mixed with dichroic pigments described later, thermotropic liquid crystal is preferred. Polymerizable liquid crystal compounds can be monomers or polymers polymerized from dimers or more.
[0082] When the polymerizable liquid crystal compound is a thermotropic liquid crystal, it can be either a thermotropic liquid crystal compound displaying a nematic liquid crystal phase or a thermotropic liquid crystal compound displaying a smectic liquid crystal phase. From the viewpoint of exhibiting high dichroism, the liquid crystal state displayed by the polymerizable liquid crystal compound is preferably a smectic phase, and if it is a higher-order smectic phase, it is even more preferable from the viewpoint of performance enhancement. Among these, higher-order smectic liquid crystal compounds that form smectic B, D, E, F, G, H, I, J, K, or L phases are more preferable, and higher-order smectic liquid crystal compounds that form smectic B, F, or I phases are even more preferable. If the liquid crystal phase formed by the polymerizable liquid crystal is one of these higher-order smectic phases, it is possible to manufacture a polarizing film with higher polarization performance. In addition, such a polarizing film with high polarization performance can produce Bragg peaks derived from higher-order structures such as hexagonal phases and crystalline phases in X-ray diffraction measurements. The Bragg peak originates from the periodic structure of molecular orientation, and films with periodic intervals of 3–6 Å can be obtained. From the viewpoint of obtaining higher polarization characteristics, it is preferable that the polarization film of the present invention comprises a polymer of polymeric liquid crystal oriented in a smectic phase.
[0083] As a polymerizable liquid crystal compound, one type can be used alone, or two or more types can be used in combination. As long as the effect of the present invention is not impaired, the polymerizable liquid crystal composition containing other compounds described later may also contain other polymerizable liquid crystal compounds besides the polymerizable liquid crystal compound. From the viewpoint of obtaining a polarizing film with high orientation order, the mass ratio of the polymerizable liquid crystal compound to the total mass of all polymerizable liquid crystal compounds contained in the polymerizable liquid crystal composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more.
[0084] Relative to the solid content of the polymeric liquid crystal composition, the content of the polymeric liquid crystal compound in the polarization film forming composition of the present invention is preferably 40 to 99.9% by mass, more preferably 60 to 99% by mass, and even more preferably 70 to 99% by mass. If the content of the polymeric liquid crystal compound is within the above range, there is a tendency for the orientation of the polymeric liquid crystal compound to increase. It should be noted that, in this specification, the solid content refers to the total amount of components after removing the solvent from the polymeric liquid crystal composition.
[0085] <Polarizing film; dichroic pigment>
[0086] Dichroic pigments are pigments that exhibit different absorbance along their long axis and short axis. Preferably, dichroic pigments possess the property of absorbing visible light, and more preferably, they have an absorption maximum wavelength (λMAX) in the range of 380–680 nm. Examples of such dichroic pigments include acridine pigments, oxazine pigments, anthocyanins, naphthalene pigments, azo pigments, and anthraquinone pigments, with azo pigments being the most preferred. Examples of azo pigments include monoazo pigments, diazo pigments, triazo pigments, tetraazo pigments, and pizoazo pigments, with diazo and triazo pigments being the most preferred. Dichroic pigments can be used alone or in combination. To achieve absorption across the entire visible light spectrum, it is preferable to combine two or more dichroic pigments, and more preferably, three or more dichroic pigments.
[0087] As azo dye, for example, compounds of formula (I) (hereinafter, sometimes referred to as "compound (I)") can be cited.
[0088] T 1 -A 1 (-N=NA) 2 ) p -N=NA 3 -T 2 (I)
[0089] In formula (I), A 1 and A 2 and A 3 The terms "T" can independently represent 1,4-phenylene, 1,4-dimethylnaphthalene, benzoic acid phenyl ester, 4,4'-diphenylenevinylene, or divalent heterocyclic groups that can have substituents. 1 and T 2 These are electron-withdrawing or electron-donating groups, positioned substantially 180° relative to the azo bond plane. p represents an integer from 0 to 4. When p is 2 or higher, each A... 2 They can be the same or different. Within the visible absorption range, the -N=N- bond can be replaced by -C=C-, -COO-, -NHCO-, and -N=CH- bonds.
[0090] From the viewpoint of obtaining good light absorption characteristics, the content of dichroic pigments (the total amount when multiple pigments are included) is typically 1 to 60 parts by mass relative to 100 parts by mass of the polymerizable liquid crystal compound, preferably 1 to 40 parts by mass, and more preferably 1 to 20 parts by mass. If the content of dichroic pigments is less than this range, light absorption becomes insufficient, and adequate polarization performance cannot be obtained; if it is more than this range, it may sometimes hinder the orientation of liquid crystal molecules.
[0091] (Indentation modulus of linear polarizer)
[0092] The indentation modulus of the linear polarizer 120 is typically below 15,000 MPa, can be below 10,000 MPa, and is suitable for being less than 10,000 MPa. Preferably, the indentation modulus of the linear polarizer 120 is below 9,900 MPa, more preferably below 9,000 MPa, further preferably below 3,000 MPa, even more preferably below 2,000 MPa, and particularly preferably below 1,000 MPa. The indentation modulus of the linear polarizer can be above 100 MPa or above, or above 300 MPa. The indentation modulus of the linear polarizer is the indentation modulus measured along a cross-section along the transmission axis.
[0093] From the viewpoint of setting the indentation modulus to the above range, linear polarizers are suitable for oriented cured products of dichroic pigments and polymeric liquid crystal compounds.
[0094] (First protective layer 110 and second protective layer 130)
[0095] The first and second protective layers each function to protect the surface of the linear polarizer. The protective layers can be resin films or resin layers. It should be noted that the first and second protective layers are arbitrary elements, but preferably at least one or both are present.
[0096] The resin film can be a monomeric film, in which case the linear polarizer and the resin film can be directly laminated together. Here, "direct lamination" includes lamination onto the linear polarizer by means of the self-adhesive properties of the resin film, and lamination via an adhesive layer or bonding agent layer. To improve the adhesion to the linear polarizer, the resin film can be surface-treated (e.g., corona treatment), or a thin layer such as a base coating (also known as an easy-to-adhere layer) can be formed.
[0097] As a resin film, for example, a resin film with excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, and tensile strength can be used. The resin film can be a thermoplastic resin film. Specific examples of such resins include: cellulose-based resins such as triacetyl cellulose; polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone-based resins; polysulfone-based resins; polycarbonate-based resins; polyamide-based resins such as nylon and aromatic polyamides; polyimide-based resins; polyolefin-based resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin-based resins having cyclic and norbornene structures (also called norbornene-based resins); (meth)acrylic resins such as polymethyl methacrylate; polyarylate-based resins; polystyrene-based resins; polyvinyl alcohol-based resins; and mixtures thereof. Thermoplastic resin films of this material are readily available from the market. In this specification, (meth)acrylic acid refers to either acrylic acid or methacrylic acid.
[0098] The thickness of the resin film is preferably 0.1 μm to 60 μm, more preferably 0.5 μm to 40 μm, and even more preferably 1 μm to 30 μm.
[0099] The resin film can be configured to be positioned closer to the viewing side than a linear polarizer. Therefore, surface treatments such as hard coating, anti-reflective treatment, anti-sticking treatment, and anti-glare treatment can be applied to the resin film as needed. Furthermore / or, treatments can be applied to the resin film to improve visibility when viewed through polarized sunglasses (typically, imparting (ellipsoidal) polarization or ultra-high phase difference). By implementing such treatments, excellent visibility can be achieved even when viewing the display image through polarized lenses such as polarized sunglasses. Therefore, polarizers with phase difference films are also suitable for use in image display devices that can be used outdoors.
[0100] A resin film can be produced by stretching a film containing the aforementioned resin. Examples of stretching processes include uniaxial stretching and biaxial stretching. Examples of stretching directions include: the mechanical flow direction (MD) of the unstretched film, a direction orthogonal to it (TD), and a direction oblique to the mechanical flow direction (MD). Biaxial stretching can be simultaneous biaxial stretching in two stretching directions, or sequential biaxial stretching where stretching occurs in a specified direction followed by stretching in other directions. The stretching process can be performed, for example, by using two or more pairs of clamping rollers with increased circumferential speed on the exit side to stretch along the length direction (mechanical flow direction: MD); or by using a chuck to hold both ends of the unstretched film and expanding it along a direction orthogonal to the mechanical flow direction (TD). In this case, the phase difference and wavelength dispersion can be controlled by adjusting the film thickness or the stretching ratio. Furthermore, the wavelength dispersion value can be controlled by adding a wavelength dispersion modifier to the resin.
[0101] The aforementioned resin film may contain any suitable additives depending on the purpose. Examples of additives include: hindered phenolic, phosphorus-based, and sulfur-based antioxidants; light stabilizers, ultraviolet absorbers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fiber and carbon fiber; near-infrared absorbers; flame retardants such as tris(dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic and inorganic fillers; resin modifiers; plasticizers; lubricants; and phase difference reducers. The types, combinations, and contents of the additives can be appropriately determined according to the purpose and desired characteristics.
[0102] In addition, to impart desired surface optical properties or other characteristics, a coating layer (surface treatment layer) can be formed on the outer surface of the resin film. Specific examples of surface treatment layers include hard coatings, anti-glare layers, anti-reflective layers, antistatic layers, and antifouling layers. There are no particular limitations on the method of forming the surface treatment layer; known methods can be used. The surface treatment layer can be formed on one side or both sides of the resin film.
[0103] When the protective layer is a thermoplastic resin layer or a curable resin layer as described later, the linear polarizer and the protective layer can be in direct contact without an adhesive layer.
[0104] For example, a composition containing a thermoplastic resin is coated onto a support substrate and dried as needed to obtain a thermoplastic resin layer with a support substrate. This thermoplastic resin layer with a support substrate is then bonded to a linear polarizer via an adhesive layer as needed. The support substrate is then peeled off, thereby allowing a thermoplastic resin layer as a protective layer to be laminated onto the linear polarizer (Method 1). Alternatively, when the protective layer is a thermoplastic resin layer, the composition can be directly coated onto the surface of the linear polarizer and dried as needed to form a thermoplastic resin layer. In this case, the linear polarizer and the protective layer are in direct contact without an adhesive layer (Method 2). In cases where the composition contains a solvent, Method 1 is preferred from the perspective of easily and stably forming a thermoplastic resin layer with a sufficiently reduced solvent content.
[0105] The protective layer can be a cured resin layer containing a curable resin. Examples of curable resins include thermosetting resins and active energy curing resins, such as (meth)acrylic resins, epoxy resins, oxetane resins, urethane resins, (meth)acrylic urethane resins, and melamine resins. The cured resin layer containing the curable resin can be formed by coating a composition containing the curable resin onto a support substrate, drying it as needed, and then heating or irradiating it with active energy rays such as visible light, ultraviolet light, infrared light, X-rays, alpha rays, beta rays, gamma rays, or electron beams. The resulting cured resin layer with the support substrate is then bonded to a linear polarizer via an adhesive layer as needed, and the support substrate is then peeled off, thereby allowing the cured resin layer as a protective layer to be laminated onto the linear polarizer.
[0106] (Transmittance of the first protective layer)
[0107] From the viewpoint of the lightfastness of the polarizing plate, it is preferable that the transmittance of the first protective layer at a wavelength of 300 nm is 5% or less, at a wavelength of 380 nm is 10% or less, at a wavelength of 400 nm is 20% or less, and at a wavelength of 450 nm is 80% or more. Furthermore, from the viewpoint of the lightfastness of the polarizing plate, the transmittance of the first protective layer at a wavelength of 400 nm is more preferably 7% or less, further preferably 5% or less, and particularly preferably 3% or less. The transmittance of the first protective layer can be measured using a UV-Vis spectrophotometer (manufactured by Shimadzu Corporation, trade name: UV-2450). To reduce the transmittance of the first protective layer at a wavelength of 400 nm, examples include: containing a UV absorber in the resin film itself, or applying a UV absorber to the surface treatment layer provided on the first protective layer.
[0108] (Moisture permeability of the first protective layer)
[0109] The moisture permeability of the first protective layer is, for example, 1700 g / m³. 2 / 24hr or less, preferably 1500g / m 2 / 24hr or less, preferably 1000g / m 2 / 24hr or less, further preferably 800g / m 2 / 24hr or less, and more preferably 500g / m 2 / 24hr or less, and further preferred to be 100g / m 2 For periods of 24 hours or less, the dosage can be 50g / m 2 / 24hr or less, it can also be 10g / m 2 / 24hr or less. If the moisture permeability of the first protective layer is 1700g / m².2 • For periods less than 24 hours, water resistance improves, inhibiting polarizer degradation. The water vapor transmission rate of the first protective layer can be determined using the following method: Using a constant temperature and humidity bath, under conditions of 40°C, 90%RH, and a measurement time of 24 hours, the water vapor transmission rate is determined using the water vapor transmission rate test method (cup method, according to JIS Z0208). The measured water vapor transmission rate is set as the water vapor transmission rate at 40°C and 90%RH [g / m³]. 2 •24hr.
[0110] (Moisture permeability of the second protective layer)
[0111] The moisture permeability of the second protective layer is, for example, 2500 g / m². 2 / 24hr or less, preferably 2000g / m 2 / 24hr or less, preferably 1700g / m 2 / 24hr or less, further preferably 1000g / m 2 / 24hr or less, and further preferred to be 100g / m 2 / less than 24hr, and further preferably 50g / m 2 / 24hr or less, it can also be 10g / m 2 / 24hr or less. The permeability is typically 1g / m³. 2 / 24hr or more, preferably 3g / m 2 / 24hr or more. If the moisture permeability of the second protective layer is 2500g / m². 2 • For temperatures below 24 hours, the transfer of components from the linear polarizer to each phase difference layer is suppressed under high-temperature conditions, exhibiting a tendency to suppress changes in the reflected hue of the optical laminate. When the second protective layer is a thermoplastic resin film, the moisture permeability of the second protective layer can be measured in the same manner as the first protective layer. Furthermore, when the second protective layer is a thermoplastic resin layer or a curable resin layer, for example, by transferring the second protective layer formed on a support substrate to an aluminum mask to prepare the test sample, measurements based on a humidity sensor method can be performed.
[0112] (Adhesive layer (adhesive layer D) 200)
[0113] The bonding layer can be an adhesive layer (also known as a pressure-sensitive adhesive) or a bonding agent layer.
[0114] (Adhesive layer)
[0115] As the adhesive composition forming the adhesive layer, conventionally known adhesive compositions with excellent optical transparency can be used without particular limitation. For example, adhesive compositions based on polymers such as acrylic resins, urethane resins, silicone resins, and polyvinyl ether resins can be used. Additionally, active energy radiation-curable adhesive compositions and thermosetting adhesive compositions can also be used. Among these, adhesive compositions based on acrylic resins with excellent transparency, adhesion, re-peelability, weather resistance, and heat resistance are particularly suitable.
[0116] The adhesive composition may further include crosslinking agents, silane compounds, antistatic agents, etc.
[0117] [(Meth)acrylic resins]
[0118] The (meth)acrylate resin contained in the adhesive composition is preferably a polymer (hereinafter also referred to as "(meth)acrylate polymer") with structural units derived from alkyl methacrylates of the following formula (I) as the main component (e.g., containing 50 parts by mass or more relative to 100 parts by mass of the structural units of the (meth)acrylate resin).
[0119] It should be noted that in this specification, (meth)acrylic resin refers to either acrylic resin or methacrylic resin, and the "(meth)" in (meth)acrylate, etc., has the same meaning.
[0120] [Chemical Formula 1]
[0121]
[0122] [In the formula, R] 10 R represents a hydrogen atom or a methyl group. 20 The alkyl group represents an alkyl group having 1 to 20 carbon atoms. This alkyl group can have any structure, including straight-chain, branched, or cyclic forms. The hydrogen atoms of this alkyl group can be substituted with alkoxy groups having 1 to 10 carbon atoms.
[0123] Examples of (meth)acrylates represented by formula (I) include: methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isohexyl methacrylate, n-heptyl methacrylate, n-octyl methacrylate, isooctyl methacrylate, 2-ethylhexyl methacrylate, n-nonyl methacrylate, isononyl methacrylate, n-decyl methacrylate, isodecyl methacrylate, n-dodecyl methacrylate, cyclohexyl methacrylate, isobornyl methacrylate, stearyl methacrylate, tert-butyl methacrylate, etc. Specific examples of alkyl acrylates containing alkoxy groups include 2-methoxyethyl methacrylate and ethoxymethyl methacrylate. Preferably, it contains n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, and particularly preferably contains n-butyl (meth)acrylate.
[0124] (Meth)acrylate polymers may contain structural units derived from other monomers besides structural unit (I). There may be one or more structural units derived from other monomers. Examples of other monomers that may be included in (meth)acrylate polymers include monomers with polar functional groups, monomers with aromatic groups, and acrylamide monomers.
[0125] Examples of monomers with polar functional groups include (meth)acrylates. Examples of polar functional groups include: hydroxyl groups; carboxyl groups; substituted or unsubstituted amino groups substituted with alkyl groups having 1 to 6 carbon atoms; heterocyclic groups such as epoxy groups.
[0126] Relative to all 100 parts by mass of the (meth)acrylate polymer, the content of structural units derived from monomers having polar functional groups in the (meth)acrylate polymer is preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, even more preferably 0.5 parts by mass or more and 5 parts by mass or less, and particularly preferably 1 part by mass or more and 5 parts by mass or less.
[0127] Examples of monomers containing aromatic groups include (meth)acrylates that have one (meth)acryloyl group and one or more aromatic rings (e.g., benzene ring, naphthalene ring, etc.) within the molecule, and also have phenyl, phenoxyethyl, or benzyl groups. By including these structural units, the whitening phenomenon of polarizers that occurs under high temperature and high humidity conditions can be suppressed.
[0128] Relative to all 100 parts by mass of the (meth)acrylate polymer, the content of structural units derived from monomers having aromatic groups in the (meth)acrylate polymer is preferably 20 parts by mass or less, more preferably 4 parts by mass or more and 20 parts by mass or less, and even more preferably 4 parts by mass or more and 15 parts by mass or less.
[0129] Examples of acrylamide monomers include N-(methoxymethyl)acrylamide, N-(ethoxymethyl)acrylamide, N-(propoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, and N-(2-methylpropoxymethyl)acrylamide. By incorporating these structural units, the exudation of additives such as antistatic agents described later can be suppressed.
[0130] In addition, structural units derived from other monomers besides structural unit (I) may also include: structural units derived from styrene monomers, structural units derived from vinyl monomers, structural units derived from monomers having multiple (meth)acryloyl groups within the molecule, etc.
[0131] The weight-average molecular weight (hereinafter, also referred to as "Mw") of the (meth)acrylic resin (1) is preferably between 500,000 and 2,500,000. If the weight-average molecular weight is 500,000 or more, the durability of the adhesive layer under high temperature and high humidity conditions can be improved. If the weight-average molecular weight is 2,500,000 or less, the operability of applying a coating liquid containing the adhesive composition becomes good. The molecular weight distribution (Mw / Mn), expressed as the ratio of weight-average molecular weight (Mw) to number-average molecular weight (hereinafter, also referred to as "Mn"), is usually 2 to 10. In this specification, "weight-average molecular weight" and "number-average molecular weight" are polystyrene conversion values determined by gel permeation chromatography (GPC).
[0132] When a (meth)acrylic resin is dissolved in ethyl acetate to prepare a 20% by mass solution, its viscosity at 25°C is preferably 20 Pa·s or less, more preferably 0.1 to 15 Pa·s. If the viscosity of the (meth)acrylic resin at 25°C is within the above range, it contributes to improving the durability and reprocessability of the polarizing plate containing the adhesive layer formed from the above resin. The above viscosity can be measured using a Brookfield viscometer.
[0133] The glass transition temperature (Tg) of the (meth)acrylic resin is, for example, -60 to 20°C, preferably -50 to 15°C, more preferably -45 to 10°C, and even more preferably -40 to 0°C. It should be noted that the glass transition temperature can be determined using a differential scanning calorimeter (DSC).
[0134] (Meth)acrylic resins may contain two or more (meth)acrylate polymers. Examples of such (meth)acrylate polymers include (meth)acrylate polymers with relatively low molecular weights, where the structural unit (I) derived from the above-mentioned (meth)acrylate is the main component and the weight-average molecular weight is in the range of 50,000 to 300,000.
[0135] (Meth)acrylic resins are typically manufactured using known polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. In the manufacture of (meth)acrylic resins, polymerization is usually carried out in the presence of a polymerization initiator. The amount of polymerization initiator used is typically 0.001 to 5 parts by mass relative to 100 parts by mass of all monomers constituting the (meth)acrylic resin. (Meth)acrylic resins can also be manufactured by polymerization using active energy rays such as ultraviolet light.
[0136] [Cross-linking agent]
[0137] The adhesive composition preferably includes a crosslinking agent. Commonly used crosslinking agents include isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc. In particular, isocyanate compounds are preferred from the viewpoints of the pot life of the adhesive composition, the crosslinking rate, and the durability of the polarizer.
[0138] Isocyanate compounds are compounds having at least two isocyanate groups (-NCO) within their molecules. Specifically, examples include: toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, phenylenediamine diisocyanate, hydrogenated phenylenediamine diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, and triphenylmethane triisocyanate. Additionally, examples include: adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane; dimers and trimers of these isocyanate compounds. Two or more isocyanate compounds can be combined.
[0139] The proportion of crosslinking agent relative to 100 parts by weight of (meth)acrylic resin is, for example, 0.01 to 10 parts by weight, preferably 0.05 to 5 parts by weight, and more preferably 0.1 to 1 parts by weight.
[0140] [Silane compounds]
[0141] The adhesive composition may further contain silane compounds.
[0142] Examples of silane compounds include: vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(2-methoxyethoxy)silane, 3-epoxypropoxypropyltrimethoxysilane, 3-epoxypropoxypropyltriethoxysilane, 3-epoxypropoxypropylmethyldimethoxysilane, 3-epoxypropoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, and 3-mercaptopropyltrimethoxysilane.
[0143] In addition, silane compounds may include oligomers derived from the aforementioned silane compounds.
[0144] The content of silane compound in the adhesive composition is typically 0.01 to 10 parts by weight relative to 100 parts by weight of (meth)acrylic resin, preferably 0.05 to 5 parts by weight. If the content of silane compound is 0.01 parts by weight or more, there is a tendency to improve the adhesion between the adhesive layer and the adherend; if the content is 10 parts by weight or less, there is a tendency to suppress the seepage of silane compound from the adhesive layer.
[0145] <Antistatic Agent>
[0146] The adhesive composition may further include an antistatic agent. Known antistatic agents are examples, and ionic antistatic agents are suitable. As the cationic component constituting the ionic antistatic agent, organic and inorganic cations are examples. As organic cations, pyridinium cations, imidazolium cations, ammonium cations, sulfonium cations, phosphonium cations, etc., are examples. As inorganic cations, alkali metal cations such as lithium cations, potassium cations, sodium cations, cesium cations, etc., and alkaline earth metal cations such as magnesium cations, calcium cations, etc., are examples. As the anionic component constituting the ionic antistatic agent, it can be any of inorganic and organic anions; from the perspective of superior antistatic performance, anionic components containing fluorine atoms are preferred. As an anionic component containing fluorine atoms, hexafluorophosphate anion (PF6) is an example. - ), bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - ], bis(fluorosulfonyl)imide anion [(FSO2)2N - Anions, etc.
[0147] From the perspective of excellent antistatic properties and long-term stability of the adhesive composition, ionic antistatic agents that are solid at room temperature are preferred.
[0148] The content of antistatic agent relative to 100 parts by weight of (meth)acrylic resin is, for example, 0.01 to 20 parts by weight, preferably 0.1 to 10 parts by weight, and more preferably 1 to 7 parts by weight.
[0149] The adhesive composition may contain, alone or in combination with two or more additives such as UV absorbers, solvents, crosslinking catalysts, tackifying resins (tackifiers), and plasticizers. Additionally, it is useful to incorporate UV-curable compounds into the adhesive composition to form an adhesive layer, which is then cured by irradiation with UV light, resulting in a harder adhesive layer.
[0150] An adhesive layer can be formed, for example, by dissolving or dispersing the above-mentioned adhesive composition in a solvent to prepare an adhesive composition containing a solvent, and then applying it to the surface of the layer to which the adhesive layer is to be formed and allowing it to dry.
[0151] The thickness of the adhesive layer is typically 0.1–30 μm, preferably 1–30 μm, and more preferably 3–25 μm.
[0152] (Adhesive layer)
[0153] The adhesive layer can be formed from an adhesive composition.
[0154] Examples of adhesive compositions include: aqueous adhesive compositions and curable adhesive compositions that are cured by heating or irradiation with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Examples of aqueous adhesive compositions include: aqueous adhesive compositions formed by dissolving a polyvinyl alcohol resin or urethane resin as a main component in water, and aqueous adhesive compositions formed by dispersing a polyvinyl alcohol resin or urethane resin as a main component in water. Aqueous adhesive compositions may further contain curing components such as polyaldehydes, melamine compounds, zirconium oxide compounds, zinc compounds, glyoxal compounds, water-soluble epoxy resins, and crosslinking agents. Examples of water-based adhesive compositions include the adhesive compositions described in Japanese Patent Application Publication No. 2010-191389, Japanese Patent Application Publication No. 2011-107686, Japanese Patent Application Publication No. 2020-172088, and Japanese Patent Application Publication No. 2005-208456.
[0155] The preferred curable adhesive composition is an active energy ray curable adhesive composition that contains a curable (polymerizable) compound as the main component and is cured by irradiation with active energy rays. Examples of active energy ray curable adhesive compositions include cationic polymeric adhesive compositions containing a cationic polymeric compound as the curing compound, free radical polymeric adhesive compositions containing a free radical polymeric compound as the curing compound, and mixed adhesive compositions containing both cationic polymeric compounds and free radical polymeric compounds as curing compounds.
[0156] Cationic polymerizable compounds are compounds or oligomers that are solidified by cationic polymerization reactions through irradiation or heating with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Specifically, examples include epoxy compounds, oxetane compounds, and vinyl compounds.
[0157] Examples of epoxy compounds include: alicyclic epoxy compounds such as 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexylcarbamate (compounds having one or more epoxy groups bonded to an alicyclic ring within the molecule); aromatic epoxy compounds such as bisphenol A diglycidyl ether (compounds having both an aromatic ring and an epoxy group within the molecule); and aliphatic epoxy compounds such as 2-ethylhexyl glycidyl ether and 1,4-butanediol diglycidyl ether (compounds having at least one ethylene oxide ring bonded to an aliphatic carbon atom within the molecule).
[0158] Examples of oxetane compounds include 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane, which contains one or more oxetane rings within its molecule.
[0159] The cationic polymerization adhesive composition preferably includes a cationic polymerization initiator. The cationic polymerization initiator can be a thermal cationic polymerization initiator or a photocationic polymerization initiator. Examples of cationic polymerization initiators include: aromatic diazonium salts such as benzenediazonium hexafluoroantimonate; aromatic iodonium salts such as diphenyliodonium tetra(pentafluorophenyl)borate; aromatic sulfonium salts such as triphenylsulfonium hexafluorophosphate; and iron-aromatic complexes such as xylene-cyclopentadienyl iron(II) hexafluoroantimonate. The content of the cationic polymerization initiator is typically 0.1 to 10 parts by weight relative to 100 parts by weight of the cationic polymerization compound. Two or more cationic polymerization initiators may be included.
[0160] Examples of cationic polymerizable adhesive compositions include those described in Japanese Patent Application Publication No. 2016-126345, International Publication No. 2019 / 10315, and Japanese Patent Application Publication No. 2021-113969.
[0161] Free radical polymerizable compounds are compounds or oligomers that are solidified through free radical polymerization reactions caused by irradiation or heating with active energy rays such as ultraviolet light, visible light, electron beams, and X-rays. Specifically, compounds with olefinic unsaturated bonds can be cited as examples. Examples of compounds with olefinic unsaturated bonds include (meth)acrylic acid compounds with one or more (meth)acryloyl groups in the molecule, and vinyl compounds with one or more vinyl groups in the molecule.
[0162] Examples of (meth)acrylic acid compounds include: (meth)acrylic acid oligomers having at least two (meth)acryloyl groups, obtained by reacting (meth)acrylic ester monomers, (meth)acrylamide monomers, and functional group-containing compounds in two or more reactions. In this specification, (meth)acryloyl group refers to either an acryloyl group or a methacryloyl group.
[0163] Free radical polymerization adhesive compositions preferably include a free radical polymerization initiator. The free radical polymerization initiator can be a thermal free radical polymerization initiator or a photofree radical polymerization initiator. Examples of free radical polymerization initiators include: acetophenone-based initiators such as acetophenone and 3-methylacetophenone; benzophenone-based initiators such as benzophenone, 4-chlorobenzophenone, and 4,4'-diaminobenzophenone; benzoin ether-based initiators such as benzoin propyl ether and benzoin ethyl ether; thioxanthone-based initiators such as 4-isopropylthioxanthone; and xanthones, fluorenone, etc. The content of the free radical polymerization initiator is typically 0.1 to 10 parts by weight relative to 100 parts by weight of the free radical polymerizable compound. Two or more free radical polymerization initiators may be included.
[0164] Examples of free radical polymerizable adhesive compositions include those described in Japanese Patent Application Publication No. 2016-126345, Japanese Patent Application Publication No. 2016-153474, and International Publication No. 2017 / 183335.
[0165] Active energy ray curable adhesive compositions may contain additives such as ion traps, antioxidants, chain transfer agents, tackifiers, thermoplastic resins, fillers, flow modifiers, plasticizers, defoamers, antistatic agents, leveling agents, and solvents, as needed.
[0166] The adhesive composition and adhesive layer are suitable for containing silicone-based or fluorine-based leveling agents. The leveling agent content in the adhesive composition and adhesive layer is preferably 0.001 to 2 parts by weight relative to 100 parts by weight of the solid components.
[0167] The bonding of the polarizer 100 and the phase difference layer laminate 600 using an adhesive layer can be performed by applying an adhesive composition to at least one bonding surface selected from the bonding surface of the polarizer 100 and the bonding surface of the phase difference layer laminate 600, overlapping the two surfaces through the adhesive composition coating layer, bonding them by pressing from above and below using a bonding roller or the like, and then drying the adhesive layer, curing it by irradiating it with active energy rays, or curing it by heating.
[0168] Before forming the adhesive layer, at least one bonding surface selected from the bonding surface of the polarizer 100 and the bonding surface of the phase difference layer laminate 600 may be subjected to easy-bonding treatments such as saponification, corona treatment, plasma treatment, primer treatment, and anchor coating treatment.
[0169] The coating layer of the adhesive composition can be formed using various coating methods such as die coating machine, comma coating machine, gravure coating machine, wire bar coating machine, and doctor blade coating machine.
[0170] The light intensity during irradiation with active energy rays is determined based on the composition of the active energy ray-cured adhesive composition and is not particularly limited, but is preferably 10 mW / cm². 2 Above and 1,000 mW / cm 2 The following should be noted: the irradiation intensity is preferably within the wavelength range effective for activating photocationic polymerization initiators or photoradical polymerization initiators. Irradiation at this intensity once or multiple times is performed, preferably with a cumulative light dose of 10 mJ / cm². 2 The above is more preferably set at 100 mJ / cm. 2 Above 2,000 mJ / cm 2 the following.
[0171] There are no particular limitations on the light source used for the polymerization and curing of active energy radiation-cured adhesive compositions. Examples include low-pressure mercury lamps, medium-pressure mercury lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, xenon lamps, halogen lamps, gallium lamps, chemical lamps, black light lamps, microwave-excited mercury lamps, and metal halide lamps.
[0172] The thickness of the adhesive layer formed by the aqueous adhesive composition can be, for example, 5 μm or less, preferably 1 μm or less, more preferably 0.5 μm or less, and can be 0.01 μm or more, preferably 0.05 μm or more.
[0173] The thickness of the adhesive layer formed by the active energy ray curable adhesive composition can be, for example, 10 μm or less, preferably 5 μm or less, more preferably 3 μm or less, or 0.1 μm or more, preferably 0.5 μm or more, more preferably 1 μm or more.
[0174] (Indentation elastic modulus of bonding layer D)
[0175] The compressive modulus of the bonding layer D is not particularly limited. From the viewpoint of suppressing deformation under high-temperature conditions, the compressive modulus of the bonding layer D is preferably 3 MPa or more, more preferably 5 MPa or more, further preferably 8 MPa or more, and even more preferably 10 MPa or more. It can be 500 MPa or more, 2000 MPa or more, or 2500 MPa or more. It is typically 6000 MPa or less, but from the viewpoint of suppressing warping of the image display device when combining the optical laminate with the image display device, it is preferable to have a compressive modulus less than that of the adhesive layer Z.
[0176] In this specification, indentation modulus refers to the DMT modulus obtained by analyzing the pull-back process of the force curve using the theory (DMT theory) based on the Derjaguim-Muller-Toporov et al. (JKR theory) or the JKR modulus obtained by analyzing the mechanical properties of the cross-section of the evaluation specimen using a scanning probe microscope (SPM). The indentation modulus is a value measured at 24°C and 41% relative humidity, according to the method described in the examples below. It should be noted that, as described in the examples, when measuring the DMT modulus for each layer of the evaluation specimen, the DMT modulus is used for layers with a DMT modulus of 1000 MPa or higher, while the JKR modulus is used for layers with a DMT modulus less than 1000 MPa.
[0177] (In-plane average refractive index of bonding layer D)
[0178] The in-plane average refractive index of the bonding layer D is not particularly limited. From the viewpoint of suppressing the reduction of the anti-reflection function of the circular polarizer, the in-plane average refractive index of the bonding layer D is preferably 1.40 or more, more preferably 1.45 or more, and even more preferably 1.50 or more. In addition, it is usually 1.70 or less.
[0179] It should be noted that, in this specification, the in-plane average refractive index of each bonding layer is the refractive index at a wavelength of 589 nm, which can be measured using an Abbe-type refractometer, a KOBRA-WR (manufactured by Oji Measurement Equipment Co., Ltd.), or similar methods. Specifically, for example, it can be measured according to the method described in the embodiments described later. The in-plane average refractive index of each plane of the phase retardation layer described later can also be measured in the same way.
[0180] (Phase difference layer stack 600)
[0181] The phase difference layer stack 600 has a λ / 2 portion 300 and a λ / 4 portion 400 sequentially from the side of the linear polarizer 120. An adhesive layer (called adhesive layer B) may also be sandwiched between the λ / 2 portion 300 and the λ / 4 portion 400.
[0182] (λ / 2 parts 300)
[0183] The λ / 2 section 300 has the function of imparting a phase difference of λ / 2 to the incident light of wavelength λ.
[0184] The λ / 2 section 300 has one pair of in-phase retardation layers (retardation layers) 310. The slow axes of the pair of in-phase retardation layers 310 are preferably aligned. "Pretty aligned" means within ±5°. That is, when viewed from the thickness direction of the optical laminate, the angle between the slow axes of the pair of in-phase retardation layers of the λ / 2 section is preferably 5° or less.
[0185] In addition to one pair of in-phase phase retardation layers 310, the λ / 2 part 300 also has at least one thickness-direction phase retardation layer (phase retardation layer) 320 between the pairs of in-phase phase retardation layers 310.
[0186] In the λ / 2 section 300, by having at least one thickness-direction phase retardation layer 320 between pairs of in-phase phase retardation layers 310, the tilt visibility of the optical stack (circular polarizer) becomes good. The number of thickness-direction phase retardation layers 320 disposed between pairs of in-phase phase retardation layers 310 can be one, two, or more than three, but one is suitable.
[0187] Specifically, an example of a stacked structure of a phase difference layer of λ / 2 portion 300 recorded from the linear polarizer side is as follows.
[0188] In-plane phase retardation layer 310 / thickness direction phase retardation layer 320 / thickness direction phase retardation layer 320 / in-plane phase retardation layer 310 (e.g.) Figure 1 )
[0189] In-plane phase retardation layer 310 / thickness direction phase retardation layer 320 / in-plane phase retardation layer 310 (e.g.) Figure 2 )
[0190] Here, the in-plane phase difference layer on the side of the linear polarizer is sometimes referred to as the first in-plane phase difference layer, and the in-plane phase difference layer on the opposite side of the linear polarizer is sometimes referred to as the second in-plane phase difference layer.
[0191] [In-plane phase décor layer 310]
[0192] The in-plane retardation layer 310 includes a layer that manifests in-plane retardation. In this specification, a layer that manifests in-plane retardation refers to a layer that has birefringence in a direction parallel to the plane of the retardation layer, and more specifically, a layer that has different optical properties due to a difference between nx and ny exceeding 0.02.
[0193] The layer that displays the in-plane phase retardation can be a layer formed by stretching or the like from a thermoplastic resin film, or it can be an optical anisotropy layer (hereinafter also referred to as "phase retardation film") of a polymer containing a polymeric liquid crystal compound that has been oriented.
[0194] The in-plane retardation layer 310 is suitable as a retardation film (hereinafter also referred to as a "λ / 4 plate") to impart a phase difference of approximately λ / 4 to incident light of wavelength λ. Approximately λ / 4 refers to the range of one-sixth to one-third of the wavelength λ. The in-plane phase difference of the λ / 4 plate can be expressed as follows.
[0195] 100nm≤Re(550)≤180nm
[0196] The suitable range for the Re(550) value of the λ / 4 plate is preferably 100 nm or more and 160 nm or less, and more preferably 110 nm or more and 150 nm or less. The in-plane phase difference value of the in-plane phase difference layer 310 can be adjusted by the thickness of the layer that displays the in-plane phase difference. Since the in-plane phase difference value is determined by the following equation (4), in order to obtain the desired in-plane phase difference value (Re(λ)), Δn(λ) and film thickness d can be adjusted. The thickness of the layer that displays the in-plane phase difference can be measured using an interferometric film thickness gauge, a laser microscope or a stylus film thickness gauge. It should be noted that when the layer that displays the in-plane phase difference is a layer formed by polymerizing a polymeric liquid crystal, Δn(λ) depends on the molecular structure of the polymeric liquid crystal compound described later.
[0197] Re(λ)=d×Δn(λ)…(4)
[0198] (In the formula, Re(λ) represents the in-plane phase difference at wavelength λnm, d represents the film thickness, and Δn(λ) represents the birefringence at wavelength λnm.)
[0199] The in-plane phase difference layer 310 can be either positive wavelength dispersion or reverse wavelength dispersion, but it is suitable for having reverse wavelength dispersion.
[0200] An in-plane phase difference layer 310 with inverse wavelength dispersion (hereinafter also referred to as "inverse dispersion") satisfies the following equation (8), and can further satisfy equation (9).
[0201] Re(450) / Re(550)≤1.00…(8)
[0202] 1.00≤Re(650) / Re(550)…(9)
[0203] If the "Re(450) / Re(550)" of the in-plane phase retardation layer 310 exceeds 1.0, the leakage light on the short-wavelength side of the circular polarizer having the in-plane phase retardation layer increases. Preferably, it is 0.7 or more and 1.0 or less, more preferably 0.80 or more and 0.95 or less, even more preferably 0.80 or more and 0.93 or less, and particularly preferably 0.82 or more and 0.92 or less. When the layer displaying the in-plane phase retardation is a layer formed by polymerizing a polymeric liquid crystal, the value of "Re(450) / Re(550)" can be arbitrarily adjusted by adjusting the mixing ratio of the polymeric liquid crystal compound, the stacking angle of the multiple optically anisotropic layers, and the phase difference value.
[0204] The in-plane phase retardation layer 310 can be a positive A-plate. The positive A-plate is a phase retardation layer in which the refractive index in each direction satisfies the relationship of equation (3). Unless otherwise specified, the slow axis of the positive A-plate is parallel to nx, and ny≈nz indicates that the difference between ny and nz is less than 0.02.
[0205] nx>ny≈nz …(3)
[0206] When the positive A plate is a λ / 4 plate, the in-plane delay Re(λ) and thickness direction delay Rth(λ) of the positive A plate at a wavelength of λnm have the relationship of Equation (5) derived from Equations (1), (2), and (3).
[0207] Rth(λ)=0.5×Re(λ)…(5)
[0208] The thickness retardation Rth(550) at a wavelength of 550 nm for the λ / 4 plate can be within the range of Equation (6).
[0209] 50nm≤Rth(550)≤90nm …(6)
[0210] The suitable value range for Rth (550) is preferably 50 nm or more and 80 nm or less, and more preferably 55 nm or more and 75 nm or less.
[0211] When the in-plane phase retardation layer is a stretched film, its thickness is typically less than 80 μm, preferably 5 μm or more and 70 μm or less, more preferably 10 μm or more and 60 μm or less. When the in-plane phase retardation layer is a layer formed by polymerizing a polymeric liquid crystal, its thickness is typically 10 μm or less, preferably 5 μm or less, more preferably 0.3 μm or more and 3 μm or less. The in-plane phase retardation layer is preferably a coating layer formed by polymerizing one or more polymeric liquid crystals.
[0212] (Indentation elastic modulus of the in-plane phase difference layer)
[0213] The indentation modulus of the in-plane retardation layer 310 is not particularly limited, but from the viewpoint of suppressing deformation under high-temperature conditions, it is suitable to be 1000 MPa or more, more suitable to be 1500 MPa or more, and even more preferably 2000 MPa or more. Alternatively, it is typically 10000 MPa or less. The indentation modulus of the in-plane retardation layer is the indentation modulus measured along a section along the slow axis.
[0214] (In-plane average refractive index of the in-plane phase retardation layer)
[0215] In one embodiment of the present invention, the in-plane average refractive index of the in-plane retardation layer 310 is preferably 1.50 to 1.70, and more preferably 1.55 to 1.65. If the in-plane average refractive index of the in-plane retardation layer 310 is within the above range, it is particularly easy to improve the light reflection suppression effect at the interface with the bonding layer B. The in-plane average refractive index of the in-plane retardation layer can be controlled by the types and combinations of the components constituting the in-plane retardation layer.
[0216] <Phase difference film>
[0217] From the perspectives of thinness and the ability to arbitrarily design wavelength dispersion characteristics, it is preferable to coat a composition containing a polymeric liquid crystal compound (hereinafter also referred to as "phase retardation film forming composition") onto a transparent substrate to form an optically anisotropic layer of a polymer containing an oriented polymeric liquid crystal compound. Furthermore, the phase retardation film forming composition may further include solvents, photopolymerization initiators, photosensitizers, polymerization inhibitors, leveling agents, and adhesion enhancers.
[0218] Phase retardation films are typically formed by coating a phase retardation film forming composition onto an alignment film (details below) formed on a substrate, and then polymerizing the polymeric liquid crystal compound contained in the composition. The phase retardation film is generally a film cured by polymeric liquid crystal compound in an aligned state. To generate a phase retardation within the viewing plane, it needs to be a cured film formed by polymerizing polymeric groups in a state where the polymeric liquid crystal compound is aligned horizontally relative to the substrate surface. In this case, if the polymeric liquid crystal compound is rod-shaped, it can be a positive A-plate; if the polymeric liquid crystal compound is disk-shaped, it can be a negative A-plate.
[0219] <Compositions for forming phase retardation films; polymeric liquid crystal compounds>
[0220] The polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition of the present invention refers to a liquid crystal compound having polymerizable groups, particularly photopolymerizable groups. Conventionally known polymerizable liquid crystal compounds can be used as such compounds. Photopolymerizable groups refer to groups capable of participating in polymerization reactions through reactive species generated by a photopolymerization initiator, such as active free radicals or acids. Examples of photopolymerizable groups include vinyl, ethoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloxy, ethylene oxide, and oxetyl. Acryloyloxy, methacryloxy, ethoxy, and oxetyl are preferred, and acryloyloxy is more preferred. The liquid crystal can be thermotropic or lyotropic; thermotropic liquid crystals are preferred from the perspective of enabling dense film thickness control. Furthermore, the ordered phase structure in the thermotropic liquid crystal can be nematic liquid crystal or smectic liquid crystal. Additionally, it can be rod-shaped or disc-shaped liquid crystal. Polymerizable liquid crystal compounds can be used alone or in combination of two or more.
[0221] From the viewpoint of exhibiting reverse wavelength dispersion, liquid crystals with a mesocrystalline structure in a T-shaped or H-shaped form that further exhibit birefringence in a direction perpendicular to the direction of the molecular long axis are preferred as polymerizable liquid crystal compounds. From the viewpoint of obtaining stronger dispersion, T-shaped liquid crystals are more preferred. Specifically, compounds represented by the following formula (I) can be cited as examples of the structure of T-shaped liquid crystals.
[0222] [Chemical Formula 2]
[0223]
[0224] In formula (I), Ar represents a divalent aromatic group that may have substituents. Preferably, the divalent aromatic group contains at least one of nitrogen, oxygen, or sulfur atoms. When the divalent group Ar contains two or more aromatic groups, these two or more aromatic groups can be bonded to each other via single bonds, -CO-O-, -O-, or other divalent bonding groups.
[0225] G 1 and G 2 Each of these groups independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group. Here, the hydrogen atom contained in the divalent aromatic group or divalent alicyclic hydrocarbon group may be replaced by a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and the carbon atom constituting the divalent aromatic group or divalent alicyclic hydrocarbon group may be replaced by an oxygen atom, a sulfur atom, or a nitrogen atom.
[0226] L 1 L 2, B 1 and B 2 are each independently a single bond or a divalent linking group.
[0227] k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1 ≤ k + l. Here, in the case of 2 ≤ k + l, B 1 and B 2 , G 1 and G 2 may be the same as or different from each other.
[0228] E 1 and E 2 each independently represent an alkanediyl group having 1 to 17 carbon atoms, wherein a hydrogen atom contained in the alkanediyl group may be substituted by a halogen atom, and -CH2- contained in the alkanediyl group may be replaced by -O-, -S-, or -COO-, and in the case of having a plurality of -O-, -S-, or -COO-, they are not adjacent to each other. P 1 and P 2 independently of each other represent a polymerizable group or a hydrogen atom, and at least one is a polymerizable group.
[0229] G 1 and G 2 each independently are preferably 1,4-phenylene diyl which may be substituted with at least one substituent selected from a halogen atom and an alkyl group having 1 to 4 carbon atoms, or 1,4-cyclohexanediyl which may be substituted with at least one substituent selected from a halogen atom and an alkyl group having 1 to 4 carbon atoms, more preferably methyl-substituted 1,4-phenylene diyl, unsubstituted 1,4-phenylene diyl, or unsubstituted 1,4-trans-cyclohexanediyl, particularly preferably unsubstituted 1,4-phenylene diyl, or unsubstituted 1,4-trans-cyclohexanediyl.
[0230] In addition, it is preferable that at least one of the plurality of G 1 and G 2 present is a divalent alicyclic hydrocarbon group, and it is more preferable that at least one of G bonded to L 1 or L 2 and G 1 and G 2 is a divalent alicyclic hydrocarbon group.
[0231] L 1 and L 2 each independently are preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 OCOR a6-、-R a7 OC=OOR a8 -、-N=N-、-CR c =CR d -、or -C≡C-. Here, R a1 ~R a8 Each independently represents a single bond, or an alkylene group having 1 to 4 carbon atoms, R c and R d L represents an alkyl group or hydrogen atom with 1 to 4 carbon atoms. 1 and L 2 Each independently is more preferably a single bond, -OR a2-1 -、-CH2-、-CH2CH2-、-COOR a4-1 -、or-OCOR a6-1 -. Here, R a2-1 R a4-1 R a6-1 Each can independently represent any one of a single bond, -CH2-, or -CH2CH2-. L 1 and L 2 Each of these can be further preferred independently as a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.
[0232] B 1 and B 2 Each is preferably a single bond, an alkylene group having 1 to 4 carbon atoms, or an -O-, -S-, or -R group. a9 OR a10 -、-R a11 COOR a12 -、-R a13 OCOR a14 - or -R a15 OC=OOR a16 -. Here, R a9 ~R a16 Each can independently represent a single bond or an alkylene group having 1 to 4 carbon atoms. B 1 and B 2 Each independently is more preferably a single bond, -OR a10-1 -、-CH2-、-CH2CH2-、-COOR a12 -1 -、or-OCOR a14-1 -. Here, R a10-1 R a12-1 R a14-1 Each can independently represent any one of a single bond, -CH2-, or -CH2CH2-. B 1 and B 2Each of these can be further preferred independently as a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.
[0233] From the viewpoint of exhibiting inverse wavelength dispersion, k and l are preferably in the range of 2 ≤ k + l ≤ 6, preferably k + l = 4, and more preferably k = 2 and l = 2. If k = 2 and l = 2, it becomes a symmetrical structure, which is therefore preferred.
[0234] E 1 and E 2 Alkadiyl groups with 1 to 17 carbon atoms are preferred, and alkadiyl groups with 4 to 12 carbon atoms are more preferred.
[0235] As P 1 or P 2 Examples of polymerizable groups include epoxy, vinyl, ethoxy, 1-chlorovinyl, isopropenyl, 4-vinylphenyl, acryloyloxy, methacryloyloxy, ethylene oxide, and oxetyl. Acryloyloxy, methacryloyloxy, ethoxy, and oxetyl are preferred, and acryloyloxy is more preferred.
[0236] Ar preferably has at least one selected from aromatic hydrocarbon rings that may have substituents, aromatic heterocycles that may have substituents, and electron-withdrawing groups. Examples of such aromatic hydrocarbon rings include benzene rings, naphthyl rings, and anthracene rings, with benzene rings and naphthyl rings being preferred. Examples of such aromatic heterocycles include furan rings, benzofuran rings, pyrrole rings, indole rings, thiophene rings, benzothiophene rings, pyridine rings, pyrazine rings, pyrimidine rings, triazole rings, triazine rings, pyrrolidine rings, imidazole rings, pyrazole rings, thiazole rings, benzothiazole rings, thienothiazole rings, oxazole rings, benzoxazole rings, and phenanthroline rings. Among these, a thiazole ring, a benzothiazole ring, or a benzofuran ring is preferred, and a benzothiazole ring is even more preferred. Furthermore, when Ar contains a nitrogen atom, the nitrogen atom preferably has π electrons.
[0237] In formula (I), N represents the total number of π electrons contained in the divalent aromatic group represented by Ar. π Preferably, the value is 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. Furthermore, it is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.
[0238] As an aromatic group represented by Ar, the following groups can be suitably cited, for example.
[0239] [Chemical Formula 3]
[0240]
[0241] In equations (Ar-1) to (Ar-23), The mark indicates the connection part, Z 0 Z 1 and Z 2 Each can independently represent a hydrogen atom, a halogen atom, an alkyl group with 1 to 12 carbon atoms, a cyano group, a nitro group, an alkyl sulfinyl group with 1 to 12 carbon atoms, an alkyl sulfonyl group with 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group with 1 to 12 carbon atoms, an alkoxy group with 1 to 6 carbon atoms, an alkyl thio group with 1 to 12 carbon atoms, an N-alkylamino group with 1 to 12 carbon atoms, an N,N-dialkylamino group with 2 to 12 carbon atoms, an N-alkylaminosulfonyl group with 1 to 12 carbon atoms, or an N,N-dialkylaminosulfonyl group with 2 to 12 carbon atoms.
[0242] Q 1 and Q 2 Each is represented independently - CR 2’ R 3’ -、-S-、-NH-、-NR 2’ -、-CO- or O-、R 2’ and R 3’ Each can be independently represented as an alkyl group having 1 to 4 hydrogen atoms or carbon atoms.
[0243] J 1 and J 2 Each can be used to represent a carbon atom or a nitrogen atom independently.
[0244] Y 1 and Y 2 Each can be independently represented by an aromatic hydrocarbon group or an aromatic heterocyclic group that can be substituted.
[0245] W 1 and W 2 Each can independently represent a hydrogen atom, cyano group, methyl group, or halogen atom, and m represents an integer from 0 to 6.
[0246] As Y 1 and Y 2 The aromatic hydrocarbon group in the compound can include phenyl, naphthyl, anthraceneyl, phenanthryl, biphenyl, and other aromatic hydrocarbon groups with 6 to 20 carbon atoms, with phenyl and naphthyl being preferred, and phenyl being more preferred. As aromatic heterocyclic groups, can include furanyl, pyrroleyl, thiopheneyl, pyridyl, thiazolyl, benzothiazolyl, and other aromatic heterocyclic groups with 4 to 20 carbon atoms containing at least one heteroatom such as a nitrogen atom, oxygen atom, or sulfur atom, with furanyl, thiopheneyl, pyridyl, thiazolyl, and benzothiazolyl being preferred.
[0247] Y 1 and Y 2Each can be independently a substituted polycyclic aromatic hydrocarbon group or a polycyclic aromatic heterocyclic group. A polycyclic aromatic hydrocarbon group refers to a fused polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. A polycyclic aromatic heterocyclic group refers to a fused polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.
[0248] Z 0 Z 1 and Z 2 Each of the following is preferably composed of a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms. 0 Further preferred are hydrogen atoms, alkyl groups having 1 to 12 carbon atoms, and cyano groups, Z. 1 and Z 2 Further preferred are hydrogen atoms, fluorine atoms, chlorine atoms, methyl groups, and cyano groups.
[0249] Q 1 and Q 2 Preferred types are -NH-, -S-, and -NR. 2’ -、-O-,R 2’ Hydrogen atoms are preferred. Among them, -S-, -O-, and -NH- are particularly preferred.
[0250] From the perspective of molecular stability, formulas (Ar-6) and (Ar-7) are preferred among formulas (Ar-1) to (Ar-23).
[0251] In formula (Ar-16) ~ (Ar-23), Y 1 It can bond with the nitrogen atom and Z 0 Together, they form an aromatic heterocyclic group. Examples of aromatic heterocyclic groups that Ar can possess, as described previously, include pyrrole rings, imidazole rings, pyrrololine rings, pyridine rings, pyrazine rings, pyrimidine rings, indole rings, quinoline rings, isoquinoline rings, purine rings, and pyrrolidine rings. This aromatic heterocyclic group may have substituents. Additionally, Y... 1 It can bond with the nitrogen atom and Z 0 Together, these are the aforementioned substituted polycyclic aromatic hydrocarbon groups or polycyclic aromatic heterocyclic groups. Examples include benzofuran rings, benzothiazole rings, and benzoxazole rings.
[0252] Among polymerizable liquid crystal compounds, those with a maximum absorption wavelength of 300–400 nm are preferred. When a photopolymerization initiator is included in the polymerizable liquid crystal composition, polymerization and gelation of the polymerizable liquid crystal compound may occur during long-term storage. However, if the maximum absorption wavelength of the polymerizable liquid crystal compound is 300–400 nm, the generation of reactive species from the photopolymerization initiator and the polymerization and gelation of the polymerizable liquid crystal compound caused by these reactive species can be effectively suppressed even when exposed to ultraviolet light during storage. Therefore, this is advantageous in terms of the long-term stability of the polymerizable liquid crystal composition, and can improve the orientation and uniformity of the resulting cured liquid crystal film. It should be noted that the maximum absorption wavelength of the polymerizable liquid crystal compound can be measured using a UV-Vis spectrophotometer in a solvent. This solvent is one capable of dissolving the polymerizable liquid crystal compound, such as chloroform.
[0253] Relative to 100 parts by weight of the solid component of the polymeric liquid crystal composition, the content of the polymeric liquid crystal compound in the polymeric liquid crystal composition is, for example, 70 to 99.5 parts by weight, preferably 80 to 99 parts by weight, more preferably 85 to 98 parts by weight, and even more preferably 90 to 95 parts by weight. If the content of the polymeric liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the resulting liquid crystal cured film. It should be noted that, in this specification, the solid component of the polymeric liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymeric liquid crystal composition.
[0254] [Thickness-direction phase décor layer 320]
[0255] The thickness-direction phase retardation layer 320 is a layer that imparts a thickness-direction phase difference to the incident light. Specifically, it can be a positive C-plate. There are no special restrictions on the positive C-plate as long as it is anisotropic in the thickness direction, but without tilting or cholesteric orientation, it is a phase retardation layer in which the refractive indices in each direction satisfy the relationship of equation (7). Unless otherwise specified, the slow axis of the positive C-plate is parallel to nz, and nx≈ny indicates that the difference between nx and ny is less than 0.02.
[0256] nx≈ny<nz …(7)
[0257] The thickness-direction phase difference Rth (550) imparted by at least one thickness-direction phase retardation layer 320 disposed between one pair of in-phase phase retardation layers 310 is preferably greater than -140 nm, more preferably -120 nm or more, further preferably -100 nm or more, even more preferably -90 nm or more, even more preferably -80 nm or more, particularly preferably -70 nm or more, particularly more preferably -65 nm or more, and even more preferably -60 nm or more. Alternatively, it can be less than -30 nm, preferably less than -35 nm, more preferably less than -40 nm, and even more preferably less than -45 nm.
[0258] For example, such as Figure 2 As shown, when a thickness direction phase difference layer 320 is disposed between two pairs of in-phase phase difference layers 310, the upper and lower limits of the thickness direction phase difference Rth (550) of the thickness direction phase difference layer 320 can be the same as the example of the thickness direction phase difference Rth (550) given by the entire thickness direction phase difference layer 320, and the thickness of the thickness direction phase difference layer 320 can be 0.6 to 6 μm.
[0259] Additionally, for example, such as Figure 1 As shown, when two thickness-direction phase retardation layers 320 are disposed between two pairs of in-phase phase retardation layers 310, the upper and lower limits of the thickness-direction phase difference Rth (550) of each thickness-direction phase retardation layer 320 can be half of the exemplified upper and lower limits of the thickness-direction phase difference Rth (550) given by the at least one thickness-direction phase retardation layer 320 as a whole. Specifically, it is preferably greater than -70nm, more preferably greater than -60nm, further preferably greater than -50nm, even more preferably greater than -45nm, even more preferably greater than -40nm, particularly preferably greater than -35nm, particularly more preferably greater than -32.5nm, and even more preferably greater than -30nm. Alternatively, it can be less than -15nm, preferably less than -17.5nm, more preferably less than -20nm, and even more preferably less than -22.5nm. The thickness of each thickness-direction phase retardation layer 320 can be 0.3 to 3μm.
[0260] It should be noted that when multiple thickness-direction phase difference layers 320 are arranged between one pair of in-phase phase difference layers 310, the thickness-direction phase difference Rth of these thickness-direction phase difference layers can be the same or different from each other.
[0261] The in-plane phase difference value Re(550) at a wavelength of 550nm in the thickness direction phase difference layer 320 is typically in the range of 0 to 10nm, preferably in the range of 0 to 5nm.
[0262] (Indentation elastic modulus of the phase difference layer in the thickness direction)
[0263] The indentation elastic modulus of the phase difference layer 320 in the thickness direction is not particularly limited. From the viewpoint of suppressing deformation under high temperature conditions, it is suitable to be 1000 MPa or more, more suitable to be 1500 MPa or more, further preferably 2000 MPa or more, and even more preferably 2500 MPa or more. In addition, it is usually 10000 MPa or less.
[0264] (In-plane average refractive index of the phase décor layer in the thickness direction)
[0265] In one embodiment of the present invention, the in-plane average refractive index of the thickness-direction retardation layer 320 is preferably 1.50 to 1.70, and more preferably 1.50 to 1.60. The in-plane average refractive index of the thickness-direction retardation layer can be controlled by the types and combinations of the components constituting the in-plane retardation layer.
[0266] The positive C plate is preferably a coating layer formed by polymerizing one or more polymeric liquid crystal compounds. More preferably, it is a rod-shaped polymeric liquid crystal compound.
[0267] Examples of rod-shaped polymeric liquid crystals include compounds represented by formulas (I), (II), (III), (IV), (V), or (VI).
[0268] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-B16-E12-B17-P12 (I)
[0269] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-A14-F11 (II)
[0270] P11-B11-E11-B12-A11-B13-A12-B14-A13-B15-E12-B17-P12 (III)
[0271] P11-B11-E11-B12-A11-B13-A12-B14-A13-F11 (IV)
[0272] P11-B11-E11-B12-A11-B13-A12-B14-E12-B17-P12 (V)
[0273] P11-B11-E11-B12-A11-B13-A12-F11 (VI)
[0274] (In the formula, A12 to A14 are each independently equivalent to A11, B14 to B16 are each independently equivalent to B12, B17 is equivalent to B11, and E12 is equivalent to E11. F11 represents a hydrogen atom, an alkyl group with 1 to 13 carbon atoms, an alkoxy group with 1 to 13 carbon atoms, a cyano group, a nitro group, a trifluoromethyl group, a dimethylamino group, a hydroxyl group, a hydroxymethyl group, a formyl group, a sulfonyl group (-SO3H), a carboxyl group, an alkoxy carbonyl group with 1 to 10 carbon atoms, or a halogen atom. The -CH2- group constituting the alkyl and alkoxy groups can be replaced by -O-.)
[0275] Relative to 100 parts by weight of the solid component of the polymeric liquid crystal composition, the content of the polymeric liquid crystal compound in the polymeric liquid crystal composition is, for example, 70 to 99.5 parts by weight, preferably 80 to 99 parts by weight, more preferably 85 to 98 parts by weight, and even more preferably 90 to 95 parts by weight. If the content of the polymeric liquid crystal compound is within the above range, it is advantageous from the viewpoint of the orientation of the resulting liquid crystal cured film. It should be noted that, in this specification, the solid component of the polymeric liquid crystal composition refers to all components after removing volatile components such as organic solvents from the polymeric liquid crystal composition.
[0276] (Orientation film)
[0277] In this specification, the alignment film has an alignment constraint force that causes the polymeric liquid crystal compound to be aligned in a desired direction.
[0278] When the in-plane retardation layer 310 and the thickness-direction retardation layer 320 are layers obtained by curing polymerizable liquid crystals, the in-plane retardation layer and the thickness-direction retardation layer are typically formed separately on an alignment film disposed on a substrate. The alignment film may be removed from the alignment film along with the substrate after the formation of the retardation layer, or it may not be removed. Therefore, in this embodiment, alignment films can be independently disposed on one side of the in-plane retardation layer and the thickness-direction retardation layer. The alignment film may be disposed on the side opposite to the linear polarizer 120 relative to each retardation film, or it may be disposed on the side opposite to the linear polarizer 120.
[0279] Alignment films facilitate the alignment of polymeric liquid crystal compounds. The alignment state varies depending on the properties of the alignment film and the polymeric liquid crystal compound, and their combination can be arbitrarily chosen. Horizontal alignment films can be used when fabricating in-plane retardation layers, while vertical alignment films can be used when fabricating thickness-direction retardation layers.
[0280] Regarding the orientation constraint force, when the orientation film is formed from an orientation polymer, it can be arbitrarily adjusted according to the surface condition and friction conditions; when it is formed from a photo-oriented polymer, it can be arbitrarily adjusted according to polarized light irradiation conditions, etc. Furthermore, liquid crystal orientation can also be controlled by selecting the surface tension, liquid crystal properties, and other physical properties of the polymerizable liquid crystal compound.
[0281] As an alignment film formed between a substrate and an optically anisotropic layer, an alignment film that is insoluble in the solvent used to form the optically anisotropic layer on the alignment film and has heat resistance in the heat treatment for solvent removal and liquid crystal alignment is preferred. Examples of alignment films include alignment films containing an alignment polymer, photoalignment films, groove alignment films, and stretch films stretched along the alignment direction. In the case of application to long, roll-shaped films, photoalignment films are preferred from the viewpoint that the alignment direction can be easily controlled.
[0282] The thickness of the alignment film is typically in the range of 10 nm to 5000 nm, preferably in the range of 10 nm to 1000 nm, and more preferably in the range of 30 nm to 300 nm.
[0283] Examples of orientation polymers used in friction-oriented films include: polyamides and gelatin-like polymers with intramolecular amide bonds, polyimides with intramolecular imide bonds and their hydrolysates such as polyamic acid, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylates. Polyvinyl alcohol is preferred. These orientation polymers can be used alone or in combination of two or more.
[0284] One method for performing friction is to bring a film of an oriented polymer, formed on the surface of a substrate by coating an oriented polymer composition onto a substrate and annealing it, into contact with a friction roller wound with a friction cloth and rotating.
[0285] Photoalignment films contain polymers, oligomers, or monomers having photoreactive groups. The photoalignment film acquires orientation confinement force by irradiating polarized light. From the viewpoint that the direction of the orientation confinement force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light, photoalignment films are more preferred.
[0286] A photoreactive group is a group that generates liquid crystal alignment capability through light irradiation. Specifically, it is a group that undergoes a light-induced molecular orientation-inducing or isomerizing reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which is the origin of liquid crystal alignment capability. Among these photoreactive groups, groups that undergo dimerization or photocrosslinking reactions are preferred from the perspective of excellent alignment. As a photoreactive group capable of undergoing such reactions, a photoreactive group having unsaturated bonds, especially double bonds, is preferred, and a group having at least one selected from carbon-carbon double bonds (C=C bond), carbon-nitrogen double bonds (C=N bond), nitrogen-nitrogen double bonds (N=N bond), and carbon-oxygen double bonds (C=O bond).
[0287] Examples of photoreactive groups with C=C bonds include vinyl, polyene, succinyl, succinyl-zole, succinyl-monoyl, chalcone, and cinnamoyl groups. Chalcone and cinnamoyl groups are preferred from the viewpoint of easy control of reactivity and the ability to exhibit orientation-restricting forces during photoorientation. Examples of photoreactive groups with C=N bonds include groups with structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups with N=N bonds include azophenyl, azonaphthyl, aromatic heterocyclic azo, diazo, and formazanyl groups, with azobenzene oxide as the basic structure. Examples of photoreactive groups with C=O bonds include benzophenone, coumarin, anthraquinone, and maleimide groups. These groups can have substituents such as alkyl, alkoxy, aryl, allyloxy, cyano, alkoxycarbonyl, hydroxyl, sulfonic acid, and haloalkyl.
[0288] When irradiating with polarized light, the polarized light can be irradiated directly from the film surface or from the substrate side and transmitted through the polarized light. Furthermore, the polarized light is particularly preferably substantially parallel. Regarding the wavelength of the irradiated polarized light, it is preferable to use a wavelength in the region where the photoreactive groups of the polymer or monomer containing photoreactive groups can absorb light energy. Specifically, UV (ultraviolet light) in the wavelength range of 250–400 nm is particularly preferred. Examples of light sources used for this polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, KrF, ArF, and other ultraviolet lasers, with high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps being more preferred. These lamps are preferred because of the high luminous intensity of ultraviolet light at a wavelength of 313 nm. By passing the light from the above-mentioned light source through a suitable polarizer, polarized light can be irradiated. As the polarizer, polarizing filters, Glatthomson prisms, Glattylene prisms, and wire-grid polarizers can be used.
[0289] (The structure of the phase difference layer of λ / 2 part 300)
[0290] In the λ / 2 section 300, an adhesive layer may be independently sandwiched between adjacent phase difference layers, that is, between phase difference layers 320 in the thickness direction, between in-plane phase difference layers 310, and between in-plane phase difference layers 310 and phase difference layers 320 in the thickness direction (hereinafter, the adhesive layer between phase difference layers in the λ / 2 section is referred to as adhesive layer A), or no adhesive layer may be sandwiched.
[0291] When an adhesive layer is sandwiched between the phase retardation layers, each surface of the adhesive layer can be in direct contact with the phase retardation layers independently, or it can be in direct contact with the alignment film of the phase retardation layers. Alternatively, when no adhesive layer is sandwiched between the phase retardation layers, the phase retardation layers can be in direct contact with each other, or one or two alignment films can be sandwiched between the phase retardation layers.
[0292] In the λ / 2 section, it is preferable that at least one pair of adjacent retardation layers (which can be between a pair of thickness-direction retardation layers or between an in-plane retardation layer and a thickness-direction retardation layer) are stacked without passing through the bonding layer A. When retardation layers are stacked through the bonding layer, the refractive index difference becomes relatively large at the interface, making interface reflection more likely. By stacking at least one pair of adjacent retardation layers without passing through the bonding layer A, the interface between the retardation layer and the bonding layer can be reduced, suppressing the increase in reflectivity of the optical laminate, i.e., the reduction in the antireflective performance of the circular polarizer.
[0293] exist Figure 1 In the λ / 2 portion 300 of the phase difference layer stack 600 of the embodiment, from the polarizer 100 side, there are sequentially an in-plane phase difference layer 310, a thickness direction phase difference layer (320), an adhesive layer A (330), a thickness direction phase difference layer 320, and an in-plane phase difference layer 310.
[0294] exist Figure 2 In the λ / 2 portion 300 of the phase difference layer stack, starting from the polarizer 100 side, there are in-plane phase difference layer 310, thickness direction phase difference layer 320, bonding layer A (330), and in-plane phase difference layer 310 in sequence.
[0295] It should be noted that, as mentioned above, in Figure 1 and Figure 2 In addition, an orientation film can also exist on each surface of each phase difference layer in the λ / 2 part 300.
[0296] It should be noted that in the λ / 2 part, the bonding layer A is arbitrary, therefore in Figure 1 and Figure 2 Alternatively, a method without adhesive layer A can also be implemented.
[0297] (Laminating layer A (330) within λ / 2 part 300)
[0298] As the bonding layer A (330), the bonding layer described in the section on bonding layer D (200) can be appropriately used. The thickness of the bonding layer A (330) can be 7 μm or less, preferably 5 μm or less, or 3 μm or less, or even less than 3 μm. By thinning the bonding layer A, the thickness of the λ / 2 portion can be adjusted to an appropriate range, suppressing the reduction of the antireflective performance of the circular polarizer.
[0299] (Indentation elastic modulus of bonding layer A)
[0300] The compressive modulus of the bonding layer A is not particularly limited. From the viewpoint of suppressing deformation under high-temperature conditions, the compressive modulus of the bonding layer A is preferably 3 MPa or more, more preferably 5 MPa or more, further preferably 8 MPa or more, even more preferably 10 MPa or more, and may also be 500 MPa or more, 2000 MPa or more, or 2500 MPa or more. However, it is typically 6000 MPa or less.
[0301] (Thickness of λ / 2 section)
[0302] In this embodiment, the thickness of the λ / 2 portion can be 5 to 80 μm. The upper limit can be 70 μm or less, 60 μm or less, 50 μm or less, 30 μm or less, 20 μm or less, or 15 μm or less. The thickness of the λ / 2 portion is particularly preferably 10 μm or less. The thickness of the λ / 2 portion can be 6 μm or more, or 7 μm or more. If the λ / 2 portion is too thick, the optical path length of the light transmitted through the circular polarizer increases, thus increasing the reflectivity of the optical laminate due to increased light scattering, and sometimes reducing its anti-reflection function when used as a circular polarizer.
[0303] The thickness of the λ / 2 portion refers to the sum of the thicknesses of each of the two outermost in-plane retardation layers 310 in the λ / 2 portion and the distances between the two outermost in-plane retardation layers 310. In the case where an alignment film is present between the two outermost in-plane retardation layers, the thickness of the alignment film is also included.
[0304] The thickness of the λ / 2 portion can be adjusted by the thickness of the in-plane phase difference layer 310, the thickness direction phase difference layer 320, and the bonding layer A, or it can be controlled by directly stacking the phase difference layers together without setting the bonding layer A or by stacking them only through the orientation layer.
[0305] From the perspective of reducing the thickness of the λ / 2 portion, the bonding layer A is suitable as a cured layer of an active energy ray-cured adhesive or an active energy ray-cured bonding agent.
[0306] The ratio of the total thickness of all bonding layers A in the λ / 2 section to the thickness of the λ / 2 section is preferably 0.75 or less, more preferably 0.50 or less, and particularly suitable to be 0.30 or less.
[0307] (Nz coefficient at wavelength 550nm in the λ / 2 region)
[0308] In this embodiment, the Nz coefficient at a wavelength of 550 nm in the λ / 2 region is preferably 0.60 or higher and less than 1.0. The Nz coefficient is preferably greater than 0.60, and can be 0.65 or higher, 0.70 or higher, or 0.75 or higher. The Nz coefficient can be 0.95 or lower, 0.90 or lower, or 0.85 or lower. If the Nz coefficient in the λ / 2 region is within the above range, the azimuth angle dependence of hue and brightness when viewed from an oblique angle can be reduced.
[0309] The Nz coefficient at a wavelength of 550 nm for the λ / 2 portion is defined by equation (13). Here, the overall in-plane delay of the λ / 2 portion at a wavelength of 550 nm is set as ReG, and the overall thickness direction delay of the λ / 2 portion at a wavelength of 550 nm is set as RthG.
[0310] Nz coefficient ≡ (RthG / ReG) + 0.5 … (13)
[0311] To set such an Nz coefficient, it is only necessary to appropriately set the in-plane phase difference of the in-plane phase difference layer, the thickness-direction phase difference of the thickness-direction phase difference layer, and the number of thickness-direction phase difference layers.
[0312] (λ / 4 parts 400)
[0313] The λ / 4 section 400 has the function of imparting a phase difference of approximately λ / 4 to incident light of wavelength λ.
[0314] The λ / 4 section 400 has at least one thickness-direction retardation layer 420 and at least one in-plane retardation layer 410 sequentially from the side closest to the linear polarizer 120. Suitablely, the λ / 4 section 400 has one or two thickness-direction retardation layers 420 and one in-plane retardation layer 410. When there is one thickness-direction retardation layer 420, it is suitable to have one thickness-direction retardation layer 420 and one in-plane retardation layer 410 sequentially from the side closest to the linear polarizer 120. Alternatively, when there are two thickness-direction retardation layers 420, it is suitable to have one thickness-direction retardation layer 420, one in-plane retardation layer 410, and one thickness-direction retardation layer 420 sequentially from the side closest to the linear polarizer 120.
[0315] As the in-plane retardation layer 410 of the λ / 4 section, the in-plane retardation layer 310 described in the λ / 2 section can be used. The in-plane retardation layer 410 of the λ / 4 section and the in-plane retardation layer 310 of the λ / 2 section can be the same or different from each other. The λ / 4 section 400 is suitable to have one in-plane retardation layer 410. In this case, the λ / 4 plate exemplified in the λ / 2 section described above is suitable to be used as the in-plane retardation layer 410 of the λ / 4 section.
[0316] The thickness direction phase retardation layer 420 of the λ / 4 section can be the thickness direction phase retardation layer 320 described in the λ / 2 section. The thickness direction phase retardation layer 420 of the λ / 4 section and the thickness direction phase retardation layer 320 of the λ / 2 section can be the same or different from each other. The λ / 4 section 400 is also suitable to have one thickness direction phase retardation layer. That is, the λ / 4 section 400 is suitable to have one in-plane phase retardation layer 410 and one thickness direction phase retardation layer.
[0317] The total phase difference value Rth(550) in the thickness direction of the phase retardation layer 420 at a wavelength of 550 nm in the λ / 4 section can be -170 nm or more, or -150 nm or more, more preferably -120 nm or more, even more preferably -100 nm or more, even more preferably -90 nm or more, even more preferably -80 nm or more, or -70 nm or more, or -65 nm or more. Furthermore, the total phase difference value Rth(550) in the thickness direction of the phase retardation layer 420 at a wavelength of 550 nm in the λ / 4 section can be 0 nm or less, or -10 nm or less, more preferably -20 nm or less, or -30 nm or less. If the phase difference value in the thickness direction is within this range, the anti-reflection characteristics from the tilt direction can be further improved.
[0318] In the case where the λ / 4 section 400 has one phase difference layer in the thickness direction, the example of the total value of the above phase difference value Rth (550) becomes the example of the phase difference value Rth (550) for each phase difference layer in the thickness direction.
[0319] When the phase retardation layer 420 in the thickness direction is a stretched film, its thickness is typically 300 μm or less, preferably 5 μm or more and 100 μm or less, and more preferably 10 μm or more and 50 μm or less. When the phase retardation layer 420 in the thickness direction is a coating layer formed by polymerizing a polymeric liquid crystal, its thickness is typically 10 μm or less, preferably 5 μm or less, and more preferably 0.3 μm or more and 3 μm or less.
[0320] The in-plane phase difference value Re(550) at a wavelength of 550nm in the thickness direction phase difference layer 420 is typically in the range of 0 to 10nm, preferably in the range of 0 to 5nm.
[0321] (The structure of the interlayer with a phase difference of 400 in λ / 4 section)
[0322] In the λ / 4 section 400, the phase difference layers that are adjacent to each other, such as the in-plane phase difference layer 410 and the thickness direction phase difference layer 420, may each be independently sandwiched with an adhesive layer (hereinafter, the adhesive layer between the phase difference layers in the λ / 4 section is referred to as adhesive layer C), or no adhesive layer may be sandwiched.
[0323] When the bonding layer C is located between the phase retardation layers, each surface of the bonding layer C can be in direct contact with the phase retardation layers independently, or it can be in direct contact with the alignment film of the phase retardation layers. Alternatively, when the bonding layer C is not sandwiched between the phase retardation layers, the phase retardation layers can be in direct contact with each other, or one or two alignment films can be sandwiched between the phase retardation layers.
[0324] In the λ / 4 section, it is preferable that at least one pair of adjacent retardation layers (e.g., between an in-plane retardation layer and a thickness-direction retardation layer) are stacked without passing through the bonding layer C. When retardation layers are stacked via the bonding layer, the refractive index difference becomes relatively large at the interface, making interface reflection more likely. By stacking adjacent retardation layers without passing through the bonding layer C, the interface between the retardation layer and the bonding layer can be reduced, suppressing the increase in reflectivity of the optical laminate, i.e., the reduction in the antireflective performance of the circular polarizer.
[0325] exist Figure 1 In the λ / 4 portion 400 of the phase difference layer stack 600 of the embodiment, a thickness direction phase difference layer 420 and an in-plane phase difference layer 410 are sequentially provided from the polarizer side, and no bonding layer C (430) is disposed between them.
[0326] exist Figure 2 In the λ / 4 portion 400 of the phase difference layer stack 600 of the embodiment, a thickness direction phase difference layer 420, an adhesive layer C and an in-plane phase difference layer 410 are sequentially provided from the polarizer side.
[0327] It should be noted that, as mentioned above, in Figure 1 and Figure 2 In addition, an orientation film can also exist on each surface of each phase difference layer in the λ / 4 section 400.
[0328] As the bonding layer C (430), the bonding layer described in the section on bonding layer D (200) can be used appropriately, and the bonding method can also be the same. The thickness of bonding layer D (200) is not limited, and can be less than 7 μm, less than 5 μm, less than 3 μm, and more preferably less than 3 μm.
[0329] (The composition of the phase difference layer stack 600)
[0330] The in-plane phase difference layers of the λ / 2 section 300 and the λ / 4 section 400 are suitable for polymers that have been oriented into polymeric liquid crystal compounds, and are λ / 4 plates with reverse wavelength dispersion.
[0331] In addition, the phase difference layers in each thickness direction of the λ / 2 part 300 and the λ / 4 part 400 are also suitable for polymers that have been oriented as polymeric liquid crystal compounds and are positive C plates.
[0332] In the phase retardation layer stack 600, at least one in-plane phase retardation layer is suitable for being stacked with any thickness direction phase retardation layer without an adhesive layer. The combination of two or more in-plane phase retardation layers and thickness direction phase retardation layers without an adhesive layer can also exist.
[0333] The in-plane phase difference layer 310 of the λ / 2 part 300 and the thickness direction phase difference layer 420 of the λ / 4 part can also be stacked between them without passing through an adhesive layer.
[0334] For example, in Figure 1 In the embodiment, the phase difference layer stack 600 contains three combinations of in-plane phase difference layers and thickness direction phase difference layers that do not pass through the bonding layer. Figure 2 In this implementation, the combination consists of two.
[0335] In addition, the phase difference layer laminate is suitable to have at least one bonding layer, which is suitable to be a cured layer of a UV-curable adhesive.
[0336] (The relationship between the slow axis of the λ / 2 section and the slow axis of the λ / 4 section and the transmission axis of the linear polarizer)
[0337] Figure 3 and Figure 4 This is a schematic diagram illustrating an example of the configuration relationship between the slow axis 300SA of the λ / 2 section 300 and the slow axis 400SA of the λ / 4 section 400 and the transmission axis 120TA of the linear polarizer 120 when viewed from the thickness direction of the optical laminate.
[0338] exist Figure 3 In this embodiment, the angle θ2 formed by the slow axis 300SA of the λ / 2 section 300 and the transmission axis 120TA of the linear polarizer 120 is approximately 15°. Approximately 15° refers to a range of 15° ± 5°. Furthermore, the angle θ3 formed by the slow axis 400SA of the λ / 4 section 400 and the transmission axis 120TA of the linear polarizer 120 is approximately 75°. Approximately 75° refers to a range of 75° ± 5°.
[0339] exist Figure 3 In the embodiment, the angle θ1 formed by the slow axis 300SA of the λ / 2 section 300 and the slow axis 400SA of the λ / 4 section 400 is approximately 60°. Approximately 60° means a range of 60° ± 5°.
[0340] exist Figure 4 In this embodiment, the angle θ2 formed by the slow axis 300SA of the λ / 2 section 300 and the transmission axis 120TA of the linear polarizer 120 is approximately 75°. Approximately 75° refers to a range of 75° ± 5°. Furthermore, the angle θ3 formed by the slow axis 400SA of the λ / 4 section 400 and the transmission axis 120TA of the linear polarizer 120 is approximately 15°. Approximately 15° refers to a range of 15° ± 5°.
[0341] exist Figure 4 In the embodiment, the angle θ1 formed by the slow axis 300SA of the λ / 2 section 300 and the slow axis 400SA of the λ / 4 section 400 is approximately 60°. Approximately 60° means a range of 60° ± 5°.
[0342] In these cases, the wavelength dispersion of the in-plane phase difference in the phase retardation layer stack is close to linear, so the phase retardation layer stack can easily impart an ideal λ / 4 phase difference over a wide range of visible light. Therefore, it achieves a neutral hue, and the image display element also exhibits excellent anti-reflective properties.
[0343] The slow axis orientation of the in-plane phasing layer 310 of each λ / 2 section 300 is preferably configured in a manner that is approximately consistent with the orientation of the slow axis 300SA of the λ / 2 section 300. Similarly, the slow axis orientation of the in-plane phasing layer 410 of the λ / 4 section 400 is approximately consistent with the orientation of the slow axis 400SA of the λ / 4 section 400. "Approximately consistent" means that the orientations of the two slow axes can be offset by approximately ±5° (the same applies below).
[0344] (Lamination layer B)
[0345] An adhesive layer B (500) can be provided between the phase difference layer of the λ / 2 part 300 and the phase difference layer of the λ / 4 part 400. For example, in Figure 1 In this method, the in-plane phase difference layer 310 on the side opposite to the linear polarizer of the λ / 2 portion 300 and the thickness-direction phase difference layer 420 of the λ / 4 portion 400 are bonded together by the bonding layer B (500). On the other hand, in Figure 2 In this configuration, no bonding layer B (500) is disposed between the in-plane phase difference layer 310 on the side opposite to the linear polarizer of the λ / 2 portion 300 and the thickness direction phase difference layer 420 of the λ / 4 portion 400.
[0346] As the bonding layer B (500), the bonding layer described in the section on bonding layer D (200) can be used, and the bonding method can be the same. The thickness of the bonding layer B is not particularly limited; it can be set to 7 μm or less, 5 μm or less, 3 μm or less, or even less than 3 μm. An alignment film can be present between the phase difference layer and the bonding layer D. The λ / 2 portion and the λ / 4 portion can also be stacked without the bonding layer.
[0347] When the bonding layer B bonds the in-plane retardation layers together, especially from the viewpoint of reducing the refractive index difference with the in-plane retardation layers which tend to have a high in-plane average refractive index and suppressing interface reflection, it is preferable that the in-plane average refractive index of the bonding layer B is 1.50 or higher. The in-plane average refractive index of the bonding layer B can be 1.52 or higher. In addition, the absolute value of the difference between the in-plane average refractive index of the in-plane retardation layer to which the bonding layer B is bonded and the in-plane average refractive index of the bonding layer B is preferably 0.10 or less, and more preferably 0.06 or less.
[0348] If the combined thickness of the λ / 2 portion, the bonding layer B, and the λ / 4 portion is 100 μm or less, it is suitable from the viewpoint of suppressing the reduction of the antireflective function of the circular polarizer. This combined thickness can be 50 μm or less, 30 μm or less, or 20 μm or less.
[0349] The average thickness of all the adhesive layers present in the λ / 2 portion, adhesive layer B, and λ / 4 portion is preferably 7 μm or less, more preferably 5 μm or less, and particularly suitable for being less than 5 μm.
[0350] (Adhesive layer Z (700))
[0351] The optical laminate 10 may have an adhesive layer Z (700) on the side opposite to the viewing side of the λ / 4 portion, i.e., on the side of the phase difference layer laminate 600 opposite to the linear polarizer. The adhesive layer Z may be the adhesive layer exemplified in the bonding layer D. The thickness of the adhesive layer Z may be 1 μm or more and 100 μm or less, and is preferably 5 μm or more and 50 μm or less.
[0352] The compressive modulus of the adhesive layer Z is not particularly limited, but it is preferably 500 MPa or less, more preferably 20 MPa or less, even more preferably 10 MPa or less, and still more preferably 5 MPa or less. It can be 3 MPa or less, or even less than 3 MPa. It is typically 0.1 MPa or more. If the compressive modulus of the adhesive layer Z is within the above range, warping of the image display device can be suppressed when the optical laminate is bonded to the image display device via the adhesive layer Z.
[0353] (Relationship of the compressive elastic modulus of the bonding layer in the phase difference layer laminate 600)
[0354] In this embodiment, it is preferable that the phase retardation layer stack 600 has five or more phase retardation layers (e.g., in...). Figure 1 The middle section contains a total of six phase retardation layers: one pair of in-plane phase retardation layers 310, one pair of thickness-direction phase retardation layers 320, one in-plane phase retardation layer 410, and one thickness-direction phase retardation layer 420. Figure 2 The structure comprises a total of five phase retardation layers: an in-plane phase retardation layer 310, a thickness-direction phase retardation layer 320, an in-plane phase retardation layer 410, and a thickness-direction phase retardation layer 420, and an bonding layer disposed between at least one pair of phase retardation layers (e.g., in...). Figure 1 The middle layer consists of bonding layer A (330) and bonding layer B (500). Figure 2 The laminate consists of bonding layers A (330) and C (430), at least one of which has an indentation modulus of elasticity of 3 MPa or higher. By making the indentation modulus of elasticity 3 MPa or higher, the indentation modulus of elasticity and the non-shrinking bonding layers suppress the shrinkage of the in-plane phase retardation layer and the thickness direction phase retardation layer under high temperature conditions, thus suppressing deformations such as curling of the optical laminate under high temperature conditions. The indentation modulus of elasticity is typically 6000 MPa or lower.
[0355] The average compressive modulus of all bonding layers disposed between the phase retardation layers in the phase retardation layer stack 600 is preferably 3 MPa or more. Preferably, this average value can be 5 MPa or more, more preferably 10 MPa or more, further preferably 500 MPa or more, particularly preferably 1000 MPa or more, and even more preferably 1500 MPa or more. In addition, this average value is typically 6000 MPa or less. If the average compressive modulus of all bonding layers is within the above range, more shrinkage of the in-plane phase retardation layer, the thickness direction phase retardation layer, and the linear polarizer can be suppressed under high temperature conditions, thus further suppressing the deformation of the optical stack under high temperature conditions.
[0356] The thickness of all bonding layers between the phase retardation layers in the phase retardation layer stack 600 is preferably 7 μm or less, and can be 5 μm or less, or 3 μm or less. It is believed that if the bonding layer has a thickness of a certain value, the stress at the interface with the phase retardation layer is evenly distributed. Therefore, even if the phase retardation layer shrinks under high temperature conditions, uneven shrinkage at the interface can be suppressed, and deformation such as curling of the optical stack can be suppressed.
[0357] (Effects)
[0358] The optical laminate according to this embodiment provides a polarizing laminate with excellent external light reflection characteristics when viewed from an oblique angle, even when there is a certain degree of in-plane deviation in the polarization degree of the polarizer. The reason for this is not yet clear, but it is believed to have the following effect.
[0359] In thickness-direction retardation layers used in components such as λ / 4, the film thickness becomes non-uniform during formation, resulting in inhomogeneous in-plane thickness-direction phase difference values (Rth). Therefore, when linear polarizers with inhomogeneous in-plane optical properties are stacked, the deviations in the optical properties of the linear polarizers and the thickness-direction phase difference are superimposed, leading to a tendency for uneven anti-reflective performance when viewed from an oblique angle. It should be noted that if the thickness-direction retardation layer is a liquid crystal retardation layer, the liquid crystal film thickness tends to become non-uniform during liquid crystal coating, thus this trend is significant.
[0360] In the optical laminate of this embodiment, even if there is a deviation in Rth of λ / 4, the anti-reflection performance is not prone to unevenness when viewed from an oblique angle.
[0361] The thickness-direction phase retardation layer compensates for the phase difference of light incident from an oblique angle over a wide angle. In the optical stack of this embodiment, by placing the thickness-direction phase retardation layer on the λ / 2 side of the λ / 4 portion, the light transmitted through the λ / 2 portion is compensated by the thickness-direction phase retardation layer and then incident on the in-plane phase retardation layer of the λ / 4 portion. Therefore, in the optical stack of this embodiment, compared to the method of compensating for the light transmitted through the in-plane phase retardation layer of the λ / 4 portion using the thickness-direction phase retardation layer, it is possible to convert light transmitted obliquely through the phase retardation layer stack into elliptically polarized light with a high ellipticity over a wider range of Rth. Therefore, it is speculated that even if the orientation of the linear polarizer is not uniform, the antireflective performance when viewed from an oblique angle is less likely to be uneven.
[0362] In particular, in the λ / 2 section, the sum of the thickness direction phase differences at 550 nm of at least one thickness direction phase difference layer is preferably -90 nm to -40 nm, and / or the number of at least one thickness direction phase difference layer in the λ / 2 section is also preferably 1. In this case, the anti-reflective performance when viewed from an oblique angle is further improved.
[0363] In addition, when the phase difference layer laminate has more than one bonding layer, if the bonding layer is a cured layer of UV-curable adhesive, it is easier to adjust the refractive index of the phase layer and the bonding layer, which is more suitable from the point of view to improve anti-reflective performance.
[0364] In addition, from the viewpoint of improved anti-reflective performance associated with a reduction in the number of interfaces, it is also suitable for at least one in-plane phase retardation layer to be stacked with phase retardation layers in any thickness direction without an adhesive layer in the phase retardation layer stacked together.
[0365] Furthermore, such optical laminates are particularly effective when the linear polarizer is a cured product of dichroic pigments and polymeric liquid crystal compounds for which it is difficult to improve the uniformity of orientation.
[0366] <Image display device>
[0367] like Figure 1 and Figure 2 As shown, the image display device 1 includes the aforementioned optical laminate 10 and a reflective image display element (such as an organic EL display element) 900. The optical laminate 10 is disposed on the viewing side of the reflective image display element 900 with the phase retardation layer laminate 600 positioned relative to the linear polarizer 120 on the side closer to the reflective image display element 900. The optical laminate can be bonded to the image display element using an adhesive layer 700.
[0368] There is no particular limitation on reflective image display devices. Examples of such devices include organic electroluminescent (organic EL) display devices, inorganic electroluminescent (inorganic EL) display devices, liquid crystal display devices, and electroluminescent display devices.
[0369] The optical stack of this embodiment is particularly effective when the sum of the thickness direction phase differences of at least one thickness direction phase difference layer in the λ / 4 section 400 and the sum of the thickness direction phase differences of the reflective image display layer are -90 to -50 nm.
[0370] Reflective image display devices can be used in mobile devices such as smartphones and tablets, televisions, digital photo frames, electronic signage, measuring or measuring instruments, office equipment, medical equipment, electronic computing devices, etc.
[0371] When such an optical laminate 10 is laminated onto an image display element 900, which is a light-reflecting layer originating from electrodes, reflections caused by electrodes can be suppressed.
[0372] [Example]
[0373] The present invention will now be described in more detail with reference to embodiments and comparative examples, but the present invention is not limited to the following embodiments. Unless otherwise specified, “%” and “parts” in the examples refer to mass % and mass parts, respectively.
[0374] (Fabrication of polarizing plate (1))
[0375] (Preparation of the first protective layer)
[0376] A temporary protective film consisting of a 15μm thick adhesive layer and a 38μm thick polyethylene terephthalate substrate film is laminated on one side of a cyclic olefin polymer (COP) film (manufactured by ZEON Corporation, Japan, ZF-14, 23μm thick).
[0377] (A surface protective layer is formed on the exposed surface of the first protective layer)
[0378] An acrylic polymer formed by reacting a sesamol-type benzotriazole compound, used as an ultraviolet absorber, with MMA, and a mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate (product name "KAYARADDPHA", manufactured by Nippon Kayaku Co., Ltd.) were mixed at a solid content mass ratio of 45:55. Four parts by weight of a polymerization initiator (Omnirad 184 manufactured by IGMresins B.V. and ESACUREONE manufactured by DKSH Japan, mass ratio 50:50) and 0.2 parts by weight of an organosilicon leveling agent (product name "BKY-UV3500", manufactured by BYK Co., Ltd.) were added, and the mixture was stirred thoroughly to prepare a composition for forming a surface protective layer.
[0379] Next, the above-mentioned surface protective layer forming composition is applied to the exposed surface of the COP film using a wire rod to form a coating film. The formed coating film is then subjected to a process of evaporating the solvent by passing dry air at 70°C through it at a flow rate of 0.5 m / s for 30 seconds, resulting in a cumulative light intensity of 200 mJ / cm² under a nitrogen atmosphere (oxygen concentration below 200 ppm). 2 The film was cured by irradiating it with ultraviolet light, thus forming a surface protective layer with a thickness of 3 μm. This resulted in a laminated film consisting of a temporary protective film on a PET substrate, an adhesive layer, a COP film, and a surface protective layer. The first protective layer, including the COP film and the surface protective layer, had a transmittance of 0.03% at 380 nm, a transmittance of 1.9% at 400 nm, and a moisture permeability of 5.5 g / m³. 2 / 24hr.
[0380] (Preparation of polarizer (1))
[0381] A polyvinyl alcohol film with a thickness of 20 μm, a degree of polymerization of 2,400, and a degree of saponification of 99.9% or higher was dry-stretched uniaxially to a stretch ratio of 4.5 times. While maintaining tension, it was immersed for 60 seconds at 28°C in a dyeing bath containing 0.05 parts by weight of iodine and 5 parts by weight of potassium iodide relative to 100 parts by weight of water.
[0382] Next, the polarizer was immersed in an aqueous boric acid solution 1 containing 5.5 parts by weight of boric acid and 15 parts by weight of potassium iodide relative to 100 parts by weight of water at 64°C for 155 seconds. Then, it was immersed in an aqueous boric acid solution 2 containing 5.5 parts by weight of boric acid and 15 parts by weight of potassium iodide relative to 100 parts by weight of water at 67°C for 30 seconds. Finally, it was washed with pure water at 3°C and dried to obtain a polarizer (1) with a thickness of 8 μm.
[0383] The obtained polarizer (1) has a visibility correction single-unit transmittance of 41.7% and a visibility correction polarization degree of 99.995%. The indentation elastic modulus of the polarizer (1) is 9800 MPa.
[0384] (Preparation of the second protective layer (1))
[0385] As the second protective layer (1), a saponified triacetyl cellulose (TAC) membrane (Fujifilm ZRG20SL, 20 μm thick) was prepared. The moisture permeability of the second protective layer (2) was 1500 g / m². 2 / 24hr.
[0386] (Fabrication of polarizing plate (1))
[0387] While peeling the temporary protective film of the PET substrate together with the adhesive layer from the laminated film with the surface protective layer obtained above, the peeled surface was corona treated and then bonded to one side of the obtained polarizer (1) using a holding roller with an aqueous adhesive. On the other side of the polarizer (1), a second protective layer (1) was bonded to the polarizer (1) using a holding roller with an aqueous adhesive. While maintaining the tension of the obtained laminate at 430 N / m, it was dried at 60°C for 2 minutes to obtain a polarizer (1) with protective films on both sides of the polarizer (1). The aqueous adhesive used here was prepared by adding 3 parts by weight of carboxyl-modified polyvinyl alcohol (Kuraray Poval KL318 manufactured by Kuraray Co., Ltd.) and 1.5 parts by weight of water-soluble polyamide epoxy resin (Sumirez Resin 650 aqueous solution with a solid content of 30% manufactured by Taoka Chemical Industry Co., Ltd.) to 100 parts of water. Thus, a polarizing plate (1) with the structure of first protective layer / water-based adhesive / polarizing plate (1) / water-based adhesive / second protective layer (1) is obtained. In this embodiment, the linear polarizing plate (1) is equivalent to the linear polarizing plate (1).
[0388] (Fabrication of polarizing plate (2))
[0389] (Preparation of the composition for polarizing film formation)
[0390] The same method was used as described in paragraph
[0192] of Japanese Patent Application Publication No. 2020-56834 to obtain a composition for forming a polarizing film.
[0391] (Fabrication of polarizing film)
[0392] The method was operated in the same manner as described in paragraphs
[0193] to
[0196] of Japanese Patent Application Publication No. 2020-56834. A polyethylene terephthalate film that had undergone a demolding treatment was prepared as a substrate film, and a cured resin layer (1.5 μm), a photo-alignment film (100 nm), and a polarizing film (2.3 μm) were formed on the demolded surface of the substrate film, thereby obtaining a laminate X. The indentation modulus of the polarizing film was 680 MPa.
[0393] (Making of the second protective layer (2))
[0394] On the surface of the polarizing film side of the laminate X, the protective layer forming composition described below is applied using a bar coater to a cured thickness of 1.5 μm. After drying, the composite is irradiated with a cumulative light intensity of 600 mJ / cm² in the UVA region under a nitrogen atmosphere using a conveyor belt ultraviolet irradiation device (lamp: "H Bulb" manufactured by Fusion UVSystems). 2 The ultraviolet light formed a second protective layer (2). Thus, a laminate Y having a substrate film, a cured resin layer, a photo-alignment film, a polarizing film, and a second protective layer (2) was obtained.
[0395] (Preparation of the composition for forming the protective layer)
[0396] The following components were mixed and stirred at 23°C for 4 hours to obtain a composition for forming a protective layer.
[0397] • CELLOXIDE 2021P: 3,4-Epoxycyclohexanecarboxylic acid 3,4-epoxycyclohexylmethyl ester (manufactured by Daicel Chemical Co., Ltd.) 32.5 parts by weight
[0398] EHPE3150: 1,2-epoxy-4-(2-epoxyethylene)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol (manufactured by Daicel Chemical Co., Ltd.) 17.5 parts by weight
[0399] • OXT-221: Bis(3-ethyl-3-oxetanebutylmethyl) ether (manufactured by Toa Synthetic Co., Ltd.) 50 parts by weight
[0400] • CPI-100P: 50% solution of propylene carbonate in triarylsulfonium hexafluorophosphate (manufactured by San-Apro Co., Ltd.) 2.5 parts by weight
[0401] SH710: Silicone-based leveling agent (manufactured by Dow Corning Toray Co., Ltd.) 0.25 parts by weight
[0402] (Fabrication of polarizing plate (2))
[0403] Next, the temporary protective film of the PET substrate, together with the adhesive layer, is peeled off from the laminated film having the surface protective layer described above, and the resulting surface is subjected to corona treatment. Using a coating machine (a bar coater manufactured by Daiichi Rika Co., Ltd.), the following adhesive composition A is applied to the corona-treated surface, and the surface of the cured resin layer obtained by peeling off the substrate film of the laminate Y is bonded using an attachment device ("LPA3301" manufactured by FUJIPLA Co., Ltd.). A UV irradiation device with a conveyor belt (using a "V Bulb" lamp manufactured by Fusion UV Systems) is used to irradiate the laminate Y from the second protective layer side with a cumulative light intensity of 1600 mJ / cm² in the wavelength region (UVV region) of 395–445 nm. 2 Visible light is emitted, causing the adhesive to cure, thereby obtaining a polarizing plate (2) having a first protective layer / adhesive layer / cured resin layer / photo-alignment film / polarizing film / second protective layer (2). In this embodiment, the polarizing film is equivalent to the linear polarizer in the polarizing plate (2).
[0404] (Adhesive composition A)
[0405] Adhesive composition A was prepared by mixing the following ingredients and then degassing the mixture.
[0406] • Neopentyl glycol diglycidyl ether (trade name: EX-211L, manufactured by Nagase ChemteX Co., Ltd.): 30 parts by weight
[0407] ·3-Ethyl-3{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane (trade name: OXT-221, manufactured by Toa Synthetic Co., Ltd.): 13 parts by weight
[0408] • Bisphenol A type epoxy resin (trade name: EP-4100E, ADEKA Co., Ltd., viscosity 13 Pa·s (temperature 25°C)): 45 parts by weight
[0409] • Aromatic oxobutane compound (trade name: TCM-104, manufactured by TRONLY): 12 parts by weight
[0410] • Cationic polymerization initiator (trade name: CPI-100_50% solution, manufactured by San-Apro Co., Ltd.): 5.5 parts by weight (actual solid content 2.75 parts by weight)
[0411] ·1,4-Diethoxynaphthalene: 1.2 parts by weight
[0412] ·9,10-Dibutoxyanthracene: 1.9 parts by weight
[0413] • Silicone-based leveling agent (trade name: KP-341, manufactured by Shin-Etsu Chemical Co., Ltd.): 0.25 parts by weight
[0414] The cured adhesive composition A has an in-plane average refractive index of 1.54 and an indentation modulus of 3000 MPa.
[0415] (Fabrication of polarizing plate (3))
[0416] (Fabrication of polarizer (2))
[0417] The polarizer (2) was obtained by operating in the same manner as described in paragraph
[0140] of Japanese Patent Application Publication No. 2022-137939.
[0418] (Fabrication of polarizing plate (3))
[0419] The polarizer (1) was replaced with the polarizer (2), and the polarizer (3) was fabricated in the same manner as the polarizer (1). In this embodiment, the polarizer (2) is equivalent to the linear polarizer in the polarizer (3).
[0420] (Fabrication of adhesive sheet including adhesive layer)
[0421] (Preparation of acrylic resin solutions)
[0422] A mixed solution of 81.8 parts ethyl acetate, 90.0 parts butyl acrylate, 5.0 parts methyl acrylate, and 5.0 parts acrylic acid was added to a reaction vessel equipped with a cooling pipe, a nitrogen inlet pipe, a thermometer, and a stirrer. While purging the air in the apparatus with nitrogen to eliminate oxygen, the internal temperature was raised to 55°C. Then, a solution containing 0.15 parts azobisisobutyronitrile (polymerization initiator) dissolved in 10 parts ethyl acetate was added. After adding the polymerization initiator, the mixture was maintained at this temperature for 1 hour. Then, while maintaining the internal temperature at 54–56°C, ethyl acetate was continuously added to the reaction vessel at a rate of 17.3 parts / hr. The addition of ethyl acetate was stopped when the concentration of the (meth)acrylic resin reached 35% by mass. The mixture was then maintained at this temperature for another 6 hours from the start of ethyl acetate addition. Finally, ethyl acetate was added to adjust the concentration of the (meth)acrylic resin to 20% by mass, thus preparing an acrylic resin solution. The obtained acrylic resin had a weight-average molecular weight (Mw) of 1.6 million and a molecular weight distribution (Mw / Mn) of 4.5. It should be noted that Mw and Mn were determined as follows: two TSKgel GMH resins manufactured by Tosoh Corporation were connected in series in a GPC apparatus.HR Using "-H(S)" as the column and tetrahydrofuran as the eluent, the determination was performed by conversion to standard polystyrene under the conditions of sample concentration of 2 mg / mL, sample introduction volume of 100 μL, temperature of 40℃, and flow rate of 1 mL / min.
[0423] (Preparation of adhesive composition)
[0424] To obtain an adhesive composition, 0.15 parts of a crosslinking agent (manufactured by Tosoh Corporation: trade name "Coronate L" (ethyl acetate solution of trimethylolpropane adduct of toluene diisocyanate (solid content concentration 75% by mass)) and 0.2 parts of a silane coupling agent (manufactured by Shin-Etsu Chemical Industry Co., Ltd.: trade name "KBM-403") were added relative to 100 parts of the solid content of the acrylic resin solution, and ethyl acetate was further added to bring the solid content concentration to 13%.
[0425] (Preparation of the adhesive layer)
[0426] Using an applicator, the adhesive composition was applied to the release-treated surface of a release liner containing a polyethylene terephthalate film ("PLR-382190" from LINTEC Corporation) to achieve a dry thickness of 25 μm. The film was then dried at 100°C for 1 minute to create an adhesive layer (adhesive sheet). Next, the surface of the adhesive layer opposite to the release liner was bonded to the release-treated surface of a release liner containing a polyethylene terephthalate film ("PET-251130" from LINTEC Corporation) to create a release liner / adhesive layer / release liner adhesive sheet. The release liner was peeled off from the adhesive sheet, and the in-plane average refractive index (wavelength 589 nm) of the adhesive layer was measured at 25°C using a multi-wavelength Abbe refractometer ("DR-M2" from ATAGO Corporation). The in-plane average refractive index of the adhesive layer was 1.47. In addition, the compressive elastic modulus of the adhesive layer obtained by the measurement method described later is 2.9 MPa.
[0427] (Preparation for in-plane phase retardation film fabrication)
[0428] (Preparation of a composition for forming an optically aligned film for forming an in-plane phase difference layer)
[0429] The photo-alignment material with the following structure (weight average molecular weight: 50,000, m:n = 50:50) was manufactured according to the method described in Japanese Patent Application Publication No. 2021-196514. Two parts of the photo-alignment material and 98 parts of cyclopentanone (solvent) were mixed as components, and the resulting mixture was stirred at 80°C for 1 hour, thereby preparing a composition for photo-alignment film formation.
[0430] Photo-oriented materials:
[0431] [Chemical Formula 4]
[0432]
[0433] (Manufacturing of polymeric liquid crystal compounds for in-plane phase reversal layers)
[0434] Polymerizable liquid crystal compounds (A1) and (A2) having the structures shown below were prepared respectively. Polymerizable liquid crystal compound (A1) was prepared in the same manner as described in Japanese Patent Application Publication No. 2019-003177. Polymerizable liquid crystal compound (A2) was prepared in the same manner as described in Japanese Patent Application Publication No. 2009-173893.
[0435] Polymerizable liquid crystal compound (A1):
[0436] [Chemical Formula 5]
[0437]
[0438] Polymerizable liquid crystal compound (A2):
[0439] [Chemical Formula 6]
[0440]
[0441] A solution was obtained by dissolving 1 mg of a polymeric liquid crystal compound (Al) in 10 mL of chloroform. This solution was added to a 1 cm long cuvette for measurement, and the sample was placed in a UV-Vis spectrophotometer (Shimadzu Corporation, "UV-2450") to measure the absorption spectrum. The wavelength at which maximum absorbance was achieved was read from the obtained absorption spectrum. The maximum absorption wavelength λmax in the wavelength range of 300–400 nm was found to be 356 nm.
[0442] (Preparation of composition (1) for forming phase difference layer)
[0443] Polymerizable liquid crystal compound (A1) and polymerizable liquid crystal compound (A2) were mixed at a mass ratio of 90:10 to obtain a mixture. 0.1 parts of leveling agent "BYK-361N" (manufactured by BM Chemie) and 3 parts of photopolymerization initiator "Irgacure OXE-03" (manufactured by BASF Japan Co., Ltd.) were added relative to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added to achieve a solids concentration of 13%. The mixture was stirred at 80°C for 1 hour, thereby preparing a phase retardation layer forming composition (1).
[0444]
[0445] (Preparation of an oriented polymer composition for forming a phase difference layer in the thickness direction)
[0446] By adding 2-butoxyethanol to Sunever SE-610 (manufactured by Nissan Chemical Industries, Ltd.), a commercially available orientation polymer, to achieve a solid content of 1%, an orientation polymer composition was obtained.
[0447] (Preparation of composition (2) for forming a phase retardation layer in the thickness direction)
[0448] The polymerizable liquid crystal compound Paliocolor LC242 (manufactured by BASF Japan), the leveling agent "BYK-361N" (manufactured by BYK-Chemie), and "Omnirad907" (manufactured by IGM Resin BV) as a photopolymerization initiator were added. Further, propylene glycol 1-monomethyl ether-2-acetic acid (PGME) was added, and the mixture was stirred at 80°C for 1 hour to prepare a phase retardation layer forming composition (2).
[0449]
[0450] Polymerizable liquid crystal compound LC242:
[0451] [Chemical Formula 7]
[0452]
[0453] (Fabrication of in-plane phase retardation film with substrate)
[0454] While conveying a 500mm wide × 100m roll of 100μm thick biaxially stretched polyethylene terephthalate (PET) film (manufactured by Diafoil Mitsubishi Resin Co., Ltd.) at a speed of 4m / min, a plasma treatment device was used to treat the film once with an output power of 0.4kW. After plasma treatment, the aforementioned photo-alignment film forming composition was applied to the surface using a die-coating machine, dried at 120°C for 2 minutes, and then irradiated with a polarized UV irradiation device at a cumulative light intensity of 100mJ / cm along a direction at 15° relative to the width direction. 2 (Cumulative light intensity at a wavelength of 313 nm in air) Polarized UV exposure was performed. The thickness of the photo-alignment film was measured to be 100 nm using an M-220 ellipsometer manufactured by Nippon Spectrophotometer Co., Ltd.
[0455] Next, using a die-coating machine, a phase retardation layer forming composition (1) was coated onto the obtained photo-alignment film. After heating and drying at 120°C for 2 minutes, it was cooled to room temperature to obtain a dried film. Next, the dried film was irradiated with a high-pressure mercury lamp under a nitrogen atmosphere at an exposure dose of 500 mJ / cm². 2 Using ultraviolet light (365nm reference), an in-plane retardation layer is formed by curing a polymeric liquid crystal compound in a horizontally oriented state relative to the substrate plane, resulting in an in-plane retardation film comprising a substrate (PET film), a photoalignment film, and the in-plane retardation layer. The thickness of the in-plane retardation layer, measured using an Olympus LEXTOLS4100 laser microscope, is 2.0 μm. The indentation modulus of the in-plane retardation layer, measured by the method described later, is 2100 MPa, and the average in-plane refractive index of the in-plane retardation layer is 1.59. Furthermore, the angle of the slow axis of the in-plane retardation layer relative to the width direction of the retardation film, when viewed from the side of the first cured liquid crystal layer, is 15°.
[0456] The surface of the in-plane retardation layer side of the substrate-coated in-plane retardation film was corona-treated, and then bonded to glass using a 25μm pressure-sensitive adhesive manufactured by LINTEC. The PET film was then peeled off. The in-plane retardation value was measured using a KOBRA-WR manufactured by Oji Measurement & Control Co., Ltd. It should be noted that the in-plane retardation values for light with wavelengths of 450nm, 550nm, and 650nm were calculated using the Cauchy dispersion formula derived from the measurement results of the in-plane retardation values for light with wavelengths of 448.2nm, 498.6nm, 548.4nm, 587.3nm, 628.7nm, and 748.6nm.
[0457] As a result, the in-plane phase differences are Re(450) = 122 nm, Re(550) = 140 nm, and Re(650) = 144 nm. The relationship between the in-plane phase differences at each wavelength is as follows, and the in-plane phase difference layer exhibits inverse wavelength dispersion.
[0458] Re(450) / Re(550) = 0.87
[0459] Re(650) / Re(550) = 1.03
[0460] (In the formula, Re(450) represents the in-plane phase difference for light with a wavelength of 450nm, Re(550) represents the in-plane phase difference for light with a wavelength of 550nm, and Re(650) represents the in-plane phase difference for light with a wavelength of 650nm.)
[0461] The in-plane phase difference layer is a positive A plate that satisfies nx>ny≈nz. It should be noted that the phase difference value Rth(λ) in the thickness direction at each wavelength was measured, and the results are Rth(450)=61nm, Rth(550)=70nm, and Rth(650)=72nm.
[0462] (Fabrication of a thickness-direction phase retardation film with a substrate)
[0463] While conveying a 500mm wide × 100m roll of biaxially stretched polyethylene terephthalate (PET) film (manufactured by Diafoil Mitsubishi Resin Co., Ltd.) with a thickness of 100μm at a speed of 4m / min, a plasma treatment device was used to treat the film once with an output power of 0.4kW. An orientation polymer composition was coated onto the plasma-treated surface using a die-coating machine and dried at 90°C for 1 minute. The thickness of the resulting orientation film was measured using a laser microscope and found to be 30nm. Next, a phase difference layer forming composition (2) for phase difference in the thickness direction was coated onto the orientation film using a die-coating machine. After drying at 90°C for 1 minute, the dried film was irradiated with a high-pressure mercury lamp under a nitrogen atmosphere at an exposure dose of 1000mJ / cm. 2 Using ultraviolet light (reference 365nm), a thickness-direction retardation film containing a substrate (PET film), an alignment film, and a thickness-direction retardation layer was obtained. The thickness of the thickness-direction retardation layer was measured using a laser microscope, and the result was a thickness of 450nm. The indentation modulus of the thickness-direction retardation layer, measured by the method described later, was 2900MPa, and the in-plane average refractive index of the thickness-direction retardation layer was 1.50. The phase difference value was measured using a KOBRA-WR manufactured by Oji Measurement Equipment Co., Ltd. The result was a positive C-plate with Re(550) = 1nm, Rth(550) = -70nm, and satisfying nx≈ny<nz. It should be noted that the phase difference value of the PET film at a wavelength of 550nm is approximately 0, and therefore has no effect on this optical property.
[0464] (Example 1)
[0465] (Fabrication of a laminated phase retardation film α with a substrate)
[0466] A photo-alignment film forming composition was applied to the surface of the thickness-direction retardation layer side of the aforementioned substrate-coated retardation film using a die-coating machine. The resulting coated film was dried at 120°C for 2 minutes and then cooled to room temperature to form a dried film. Then, a UV irradiation device (SPOT CURE SP-9; manufactured by USHIO Electric Co., Ltd.) was used with a cumulative light intensity of 100 mJ / cm². 2(Cumulative light intensity at a wavelength of 313 nm in air) A photo-alignment film was obtained by irradiating the film with polarized UV light at a 75° angle relative to the width direction. The thickness of the photo-alignment film was measured to be 100 nm using an M-220 ellipsometer manufactured by Nippon Spectrophotometer Co., Ltd.
[0467] The above-mentioned liquid crystal phase reversal layer forming composition (1) for in-plane phase reversal layer was coated onto the obtained photoalignment film using a die-coating machine to form a coated film. The coated film was then heated and dried at 120°C for 2 minutes and cooled to room temperature to obtain a dried film. Next, the dried film was irradiated with a nitrogen atmosphere using a high-pressure mercury lamp (Unicure VB-15201BY-A, manufactured by USHIO Electric Co., Ltd.) at an exposure dose of 500 mJ / cm². 2 Using ultraviolet light (based on 365 nm), an in-plane retardation layer is formed by curing a polymeric liquid crystal compound in a horizontally oriented state relative to the substrate plane. This results in a stacked retardation film α comprising a substrate, an alignment film, a thickness-direction retardation layer, a photoalignment film, and an in-plane retardation layer. The in-plane retardation layer has a Re(550) of 140 nm and a Rth(550) of 70 nm. The thickness of the in-plane retardation layer, measured using a LEXTOLS4100 laser microscope manufactured by Olympus Corporation, is 2.0 μm. Furthermore, when viewed from the in-plane retardation layer side, the slow axis of the in-plane retardation layer is 75° relative to the width direction of the stacked retardation film α with the substrate.
[0468] (Fabrication of a stacked phase retardation film β with a substrate)
[0469] The angle between the slow axis of the in-plane retardation layer and the width direction of the retardation film, when viewed from the side of the in-plane retardation layer, was changed to 105°. Otherwise, the same operation was performed as with the substrate-coated stacked retardation film α to fabricate the substrate-coated stacked retardation film β.
[0470] (Fabrication of a laminated phase retardation film γ with a substrate)
[0471] Hereinafter, the laminated phase retardation films γ-1 to γ-3 with substrates will be collectively referred to as laminated phase retardation films γ with substrates.
[0472] (Fabrication of the laminated phase retardation film γ-1 with substrate)
[0473] By changing the Rth (550) of the thickness direction phase retardation layer to -90 nm and changing the angle of the slow axis of the in-plane phase retardation layer relative to the width direction of the phase retardation film when viewed from the side of the in-plane phase retardation layer to 165°, the same operation was performed as for the substrate-supported stacked phase retardation film α to fabricate a substrate-supported stacked phase retardation film γ-1.
[0474] (Fabrication of a laminated phase retardation film γ-2 with a substrate)
[0475] The angle between the slow axis of the in-plane retardation layer and the width direction of the retardation film, when viewed from the side of the in-plane retardation layer, was changed to 165°. Otherwise, the same operation was performed as with the substrate-supported stacked retardation film α to fabricate the substrate-supported stacked retardation film γ-2.
[0476] (Fabrication of γ-3 laminated phase retardation film with substrate)
[0477] By changing the Rth (550) of the thickness direction phase retardation layer to -40 nm and changing the angle of the slow axis of the in-plane phase retardation layer relative to the width direction of the phase retardation film when viewed from the side of the in-plane phase retardation layer to 165°, the same operation was performed as for the substrate-supported stacked phase retardation film α to fabricate a substrate-supported stacked phase retardation film γ-3.
[0478] (Fabrication of layer A-1)
[0479] Corona treatment was performed on the surface of the second protective layer (1) side of the polarizer (1). Adhesive composition A was applied to the corona-treated surface of the second protective layer (1) using a coating machine (a bar coater manufactured by Daiichi Rika Co., Ltd.) to form a layer of adhesive composition A. Next, corona treatment was performed on the surface of the in-plane retardation layer side of the laminated retardation film α with a substrate, and the corona-treated surface was bonded to the layer of adhesive composition A using an attachment device ("LPA3301" manufactured by FUJIPLA Co., Ltd.). A UV irradiation device with a conveyor belt (using a "V Bulb" lamp manufactured by Fusion UV Systems Co., Ltd.) was used to irradiate the substrate side with a cumulative light intensity of 1600 mJ / cm² in the wavelength region (UVV region) of 395–445 nm. 2 Visible light is used to cure the adhesive, thereby obtaining laminate A-1. At this time, it is implemented such that the angle between the transmission axis of the linear polarizer and the slow axis of the in-plane phase difference layer is 75°.
[0480] (The fabrication of layer B-1)
[0481] The in-plane phase retardation layer side surface of the laminated phase retardation films γ (γ1 to γ3) with substrate is bonded to the adhesive surface of a self-adhesive surface protective film (TORAY ADVANCED FILM Co., Ltd., "TORETEC (registered trademark) R304C", thickness: 30 μm). Using the same method as described above, the surface of the substrate (alignment film residue) peeled from the phase retardation film γ side of the obtained laminate is bonded to the in-plane phase retardation layer side surface of the laminated phase retardation film β with substrate using adhesive composition A, resulting in three laminates B-1. At this time, the laminations are bonded such that the slow axes of the in-plane phase retardation layers of the phase retardation films β and γ form an angle of 60° with each other.
[0482] (Fabrication of circular polarizing plates with isolation films (1-1), (1-2) and (1-3))
[0483] The substrate (alignment film residue) is peeled off from the β side of the laminated retardation film with substrate from laminates A-1 and B-1, and their surfaces are bonded together using adhesive composition A in the same manner as described above. At this time, the slow axis of the in-plane retardation layer on the linear polarizer side of laminate B-1 is aligned with the slow axis of the in-plane retardation layer in laminate A-1. In the resulting laminate, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion is 75°, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion is 15°, and the angle between the λ / 2 portion and the λ / 4 portion is 60°.
[0484] The self-adhesive surface protective film on the γ side of the laminated phase retardation film with substrate is peeled off from the obtained laminate, and the peeled side of the release film is attached to the adhesive layer. Thus, circular polarizing plates (1-1), (1-2), and (1-3) with release films are produced.
[0485] It should be noted that the thickness of the adhesive layer formed by curing the above-mentioned adhesive composition A was measured, and the result was 1.5 μm. The layer composition is shown in Table 3. It should be noted that A represents a reverse wavelength dispersive positive A plate, and the angle in parentheses following A represents the angle between the slow axis of the linear polarizer and the slow axis of the positive A plate. C represents a positive C plate, and the value in parentheses following C represents the phase difference value in the thickness direction at a wavelength of 550 nm.
[0486] (Example 2)
[0487] (Fabrication of a stacked phase retardation film δ with a substrate)
[0488] By changing the Rth (550) of the phase retardation layer in the thickness direction to -60 nm, and otherwise operating in the same manner as the substrate-supported stacked phase retardation film α, a substrate-supported stacked phase retardation film δ was fabricated.
[0489] (Fabrication of stacked phase retardation films ε (ε1~ε3) with substrate)
[0490] By changing the Rth(550) of the phase retardation layer in the thickness direction to -90nm, -70nm, and -40nm, respectively, and otherwise operating in the same manner as the substrate-supported stacked phase retardation film α, stacked phase retardation films ε-1, ε-2, and ε-3 were fabricated. Hereinafter, the substrate-supported stacked phase retardation films ε-1 to ε-3 will be collectively referred to as substrate-supported stacked phase retardation films ε.
[0491] (Fabrication of circular polarizing plates with isolation films (2-1), (2-2) and (2-3))
[0492] Using the same method as in Example 1, the surface of the second protective layer (1) side of the polarizer (1) is bonded to the surface of the in-plane phase retardation layer side of the laminated phase retardation film δ with substrate using adhesive composition A, forming a laminate A-2. This is performed such that the angle between the transmission axis of the linear polarizer and the slow axis of the in-plane phase retardation layer of the laminated phase retardation film δ with substrate is 75°.
[0493] Next, using the same method as described above, adhesive composition A is used to attach the surface of the in-plane retardation layer side of the laminated retardation film ε with substrate to the surface from which the substrate (alignment film residue) has been peeled off from the laminate A-2. This is performed such that the angle between the transmission axis of the linear polarizer and the slow axis of the in-plane retardation layer of the in-plane retardation film is 75°.
[0494] Using the same method as described above, adhesive composition A is used to adhere the surface of the in-plane retardation layer side of the above-mentioned substrate-bearing in-plane retardation film to the surface after the substrate on the thickness direction retardation film side of the obtained laminate has been peeled off (alignment film residue). At this time, the angle between the transmission axis of the linear polarizer and the slow axis of the in-plane retardation layer of the in-plane retardation film is 15°. Therefore, in the obtained laminate, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion is 75°, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion is 15°, and the angle between the λ / 2 portion and the λ / 4 portion is 60°.
[0495] The substrate on the side of the phase difference film within the peeling surface of the obtained laminate was peeled off, and the adhesive layer was bonded to the peeled-off side of the separator film. Thus, circular polarizers with separator films (2-1), (2-2), and (2-3) were fabricated.
[0496] (Example 3)
[0497] By changing the polarizing plate (1) to the polarizing plate (2), and otherwise operating in the same manner as in Example 2, circular polarizing plates (3-1), (3-2) and (3-3) with isolation films were made.
[0498] (Examples 4-6)
[0499] The Rth (550) of the phase retardation layer in the thickness direction of the stacked phase retardation film δ with substrate was changed to the values recorded in Tables 3 and 4 (-40nm, -70nm, -100nm respectively). Otherwise, the same procedure as in Example 3 was followed to fabricate each circular polarizer with an isolation film.
[0500] (Example 7)
[0501] The Rth (550) of the phase retardation layer in the thickness direction of the phase retardation film α and the phase retardation film β was changed to -50 nm. Otherwise, the same procedure as in Example 1 was followed to fabricate circular polarizers (7-1), (7-2) and (7-3) with isolation films.
[0502] (Comparative Example 1)
[0503] (Fabrication of a laminated phase retardation film φ with a substrate)
[0504] The angle between the slow axis of the in-plane retardation layer and the width direction of the retardation film, when viewed from the side of the in-plane retardation layer, was changed to 15°. Otherwise, the same operation was performed as with the substrate-supported stacked retardation film α to fabricate the substrate-supported stacked retardation film φ.
[0505] (Fabrication of a laminated phase retardation film γ with a substrate)
[0506] The angle between the slow axis of the in-plane retardation layer and the width direction of the retardation film, when viewed from the side of the in-plane retardation layer, was changed to 165°. Otherwise, the same operation was performed as with the substrate-coated stacked retardation film α to fabricate the substrate-coated stacked retardation film γ.
[0507] (Fabrication of layer A-8)
[0508] Using the same method as in Example 1, the surface of the second protective layer (1) side of the polarizer (1) is bonded to the surface of the in-plane phase retardation layer side of the laminated phase retardation film φ with substrate using adhesive composition A, forming a laminate A-8. This is performed with the angle between the transmission axis of the linear polarizer and the slow axis of the in-plane phase retardation layer of the phase retardation film φ being 15°.
[0509] (The fabrication of layer B-8)
[0510] Next, using the same method as described above, adhesive composition A is used to bond the surface of the in-plane retardation layer side of the laminated retardation film γ with the substrate to the surface of the in-plane retardation layer side of the retardation film ε (ε1~ε3) with the substrate, forming a laminate B-8. In this case, the slow axis of the in-plane retardation layers of the retardation film γ and the retardation film ε forms an angle of 60° with each other.
[0511] (Fabrication of a circular polarizing plate (8) with an isolation film)
[0512] The substrate (alignment film residue) is peeled off from the γ side of the retardation film of laminates A-8 and B-8, and their surfaces are bonded together using adhesive composition A in the same manner as described above. At this time, the laminations are aligned such that the slow axis of the in-plane retardation layer on the linear polarizer side of laminate B-8 coincides with the slow axis of the in-plane retardation layer in laminate A-8. In the resulting laminate, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion is 15°, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion is 75°, and the difference between the angles of the λ / 2 and λ / 4 portions is 60°.
[0513] The substrate on the ε side of the phase retardation film was peeled off from the obtained laminate, and the peeled-off side of the adhesive layer was bonded to the adhesive layer. Thus, circular polarizers (8-1), (8-2), and (8-3) with isolation films were fabricated.
[0514] (Example for reference)
[0515] By changing the polarizing plate (1) to the polarizing plate (3), and otherwise operating in the same manner as in Comparative Example 1, circular polarizing plates (9-1), (9-2) and (9-3) with isolation films were made.
[0516] The composition and evaluation of Comparative Example 1 and Examples 1-4 are shown in Table 3, and the composition and evaluation of Examples 5-7 and Reference Examples are shown in Table 4.
[0517] (evaluate)
[0518] (Measurement of reflectance)
[0519] The reflectance of the circular polarizer was measured using the SCI mode of a display measurement system (“DMS803”, manufactured by Instrument Systems). During measurement, the release liner of the adhesive layer of each circular polarizer with a release liner was peeled off, and the peeled surface was attached to a reflector (reflectivity: ≥96%, diffuse reflectivity: ≤9%). Measurement light was then incident from the side of the circular polarizer, and the measurement was performed.
[0520] Reflectance L* represents the reflectance at a tilt angle θ = 50°. The average value of each L* obtained by measuring the azimuth angle φ within the range of 0° to 350°, changing it every 10° from 0°, is set as Ave.L*, and evaluated according to the following criteria. In each embodiment, comparative example, and reference example, the thickness direction phase difference layer of the λ / 4 portion has three polarizing plates with Rth(550) of -90nm, -70nm, and -40nm respectively, and therefore Ave.L* was measured for each.
[0521] (Evaluation criteria for Ave.L*)
[0522] “A”: Ave.L*≤32.6
[0523] "B": 32.6<Ave.L*≤34.0
[0524] “C”: 34.0 < Ave.L*
[0525] In addition, the three Ave.L* values obtained from the three circular polarizers produced in each embodiment were measured, and the L*max-L*min values were calculated when the maximum value was set to L*max and the minimum value was set to L*min. The results were evaluated according to the following criteria.
[0526] (Evaluation benchmark of L*max-L*min)
[0527] “A”: L*max - L*min < 0.6
[0528] "B": 0.6≤L*max-L*min<2.0
[0529] “C”: 2.0 ≤ L*max - L*min
[0530] (Overall evaluation)
[0531] For each embodiment, for each evaluation of the three Ave.L* and L*max-L*min, A is set to 1 point, B to 2 points, and C to 3 points, and the total score is calculated. The total score of each embodiment is evaluated according to the following criteria.
[0532] (Evaluation criteria for comprehensive evaluation)
[0533] "A": The overall score is 4 points.
[0534] "B": The overall score is 5 points.
[0535] "C": The overall score is 6 points.
[0536] "D": A total score of 7 or higher but below 10.
[0537] "E": Overall score of 11 points or above
[0538] (Determination of the visibility-corrected polarization degree Py of polarizers (1), (2) and polarizing films)
[0539] Eight 30mm × 30mm sections were randomly cut from the prepared polarizers (1), (2) and polarizing film, and an alkali-free glass plate (Corning Corporation trade name "Eagle XG", thickness 0.7mm) was bonded to them with an adhesive layer to obtain the measurement sample. The measurement sample was set up in a spectrophotometer with an integrating sphere (Japan Spectrophotometer Co., Ltd. "V7100", 2-degree field of view; C light source) to measure Py. The measurement sample was set up with the incident light entering from the side opposite to the alkali-free glass plate. The standard deviation of each Py value was calculated and recorded in Tables 3 and 4.
[0540] It should be noted that the degree of polarization is defined by the following formula.
[0541] Degree of polarization (λ)=100×(Tp(λ)-Tc(λ)) / (Tp(λ)+Tc(λ))
[0542] Tp(λ) is the transmittance (%) when measured with respect to linearly polarized light with incident wavelength λnm using the parallel Nicol relation, and Tc(λ) is the transmittance (%) when measured with respect to linearly polarized light with incident wavelength λnm using the orthogonal Nicol relation.
[0543] The visibility-corrected polarization degree Py is obtained by correcting the polarization degree (λ) at each wavelength using the 2-degree field of view (C light source) of the JlS Z 8701. Py is measured in 5 nm increments within the wavelength range of 380–780 nm.
[0544] (In-plane average refractive index of the cured layer (adhesive layer) of adhesive composition A)
[0545] Using an adhesive coating apparatus (manufactured by Daiichi Rika Co., Ltd.), adhesive composition A was applied to one side of a stretched norbornene resin film ("Zeonor Film" manufactured by ZEON Co., Ltd., Japan) to achieve a thickness of approximately 30 μm after ultraviolet irradiation. An ultraviolet irradiation apparatus (manufactured by Fusion UV Systems Co., Ltd.) was used to apply the adhesive composition A to the surface of the film. The cumulative light intensity was 600 mJ / cm². 2 An adhesive layer was obtained by irradiating the adhesive layer with ultraviolet light (UV-B). The norbornene resin film was peeled off from the obtained adhesive layer, and the refractive index (589 nm) of the adhesive layer was measured at 25°C using a multi-wavelength Abbe refractometer (ATAGO Corporation "DR-M2"). This value was taken as the in-plane average refractive index of the cured layer of adhesive composition A.
[0546] (In-plane average refractive index of the in-plane phase retardation layer and the thickness-direction phase retardation layer)
[0547] The in-plane retardation film with substrate and the thickness-direction retardation film with substrate prepared above are bonded to a glass plate (thickness 0.7 mm, Corning "Eagle XG"). Using this laminate, the in-plane refractive indices nx and ny at 589 nm are measured using a KOBRA-WR instrument manufactured by Oji Measurement Equipment Co., Ltd. Using nx and ny, the in-plane average refractive index n is calculated according to the following formula.
[0548] n = (nx + ny) / 2
[0549] (In the formula, nx represents the refractive index in the slow axis direction within the film surface, ny represents the refractive index in the fast axis direction within the film surface, and n represents the in-plane average refractive index.)
[0550] (Indented elastic modulus)
[0551] (Production of the experimental film)
[0552] A portion of each of the circular polarizers with release films obtained in the examples and comparative examples was cut and resin-embedded so that the cross-section in the thickness direction could be observed. Next, a glass blade and a SYM blade (Shintec "SYM2045 Ultra Cryo / Wet" (model: SYM2045C)) were mounted on a microtome equipped with a Leica EMFC7 cryosectioning system. After the resin-embedded film, glass blade, and SYM blade reached a cooling temperature of -100°C, they were left to stand for 10 minutes. Then, the blade of the glass blade was scanned in a direction perpendicular to the surface of each circular polarizer with release films. After reaching the surface of the resin-embedded circular polarizer with release films, a cut of at least 100 μm was made in the depth direction of the test piece (the plane direction relative to the circular polarizer with release films). Next, using the blade of the SYM blade, a cut of 100 nm / 0.6 mm was made. -1 The stepping (Japanese original: ピッチ) cutting is 1μm or larger, and further improved to 50nm / 0.6mms. -1 The step-cutting depth is above 0.5μm, and finally, it is 30nm / 0.3mms. -1The step-cutting depth is 0.3 μm or greater. The resulting test piece is left to stand under a nitrogen atmosphere until it returns to room temperature. The cut cross-section is used as the observation surface, and the resulting test piece is placed on an SPM (Bruker; Dimension Icon). It should be noted that the cut cross-section (observation surface) is the surface along the slow axis of the first in-plane retardation layer. For the in-plane retardation layer, the thickness-direction retardation layer, the adhesive layer, and the binder layer, the indentation elastic modulus is obtained according to the following steps. The indentation elastic modulus of the in-plane retardation layer is the value measured for the first in-plane retardation layer, i.e., the indentation elastic modulus in the cross-section along the slow axis. In addition, for linear polarizers, the cross-section along each transmission axis is used as the observation surface for measurement.
[0553] (Obtaining the indentation modulus based on SPM)
[0554] The mechanical properties of the specimen cross-section were evaluated under the following conditions, and the indentation modulus was calculated based on the JKR (Johnson-Kendall-Roberts) theory and the DMT (Derjaguim-Muller-Toporov) theory. Specifically, firstly, the displacement of the piezoelectric scanner and the warping of the cantilever were measured during the contact process between the cantilever probe and the specimen, resulting in a curve (force curve) representing the relationship between the load F and the specimen deformation δ. At each measurement point, for the pull-back process of the obtained force curve (from the moment the cantilever probe presses the specimen into the pre-set maximum load until the probe completely leaves the specimen surface), the indentation modulus was first calculated analytically based on the DMT theory. For layers with an indentation modulus less than 1000 MPa, the indentation modulus obtained analytically based on the JKR theory was used. In this embodiment, the indentation modulus based on the JKR theory was used only for the adhesive layer.
[0555] In the analysis, using the analytical software (NanoScope Analysis ver. 2.00), with the DMT theoretical formula, the minimum to maximum F value during the pull-back process of the force curve was set to 0 to 1, and a fit was performed within the range of 0.05 to 0.7 to calculate the indentation modulus. With the JKR theoretical formula, a fit was performed within the range of the minimum F value during the pull-back process to 0nN to calculate the indentation modulus. For each layer constituting the laminate, the indentation modulus was calculated above 1024 points, and the average indentation modulus was calculated and used as the indentation modulus of each layer.
[0556] The cantilever used was an RTESA-300 (manufactured by Bruker; nominal elastic constant 40 N / m, nominal probe tip radius 8 nm). The elastic constant of the cantilever was calculated using the Sader Method (Reference A) integrated into the SPM device. The probe tip radius of the cantilever was calculated using the Reconstruction Method (Reference B) integrated into the SPM device, at a position 2 nm above the tip. Only cantilevers with values below 15 nm were used for measurement.
[0557] When a layer with an indentation modulus lower than 1000 MPa, obtained analytically based on the DMT theory, was detected, the cantilever was changed to an RTESA-150 (manufactured by Bruker; nominal elastic constant 5 N / m, nominal probe tip radius 8 nm), and the layer was measured again. The elastic constant of the cantilever and the probe tip diameter were calculated using the same method as described above, except that the probe tip diameter was taken at the position of the average specimen deformation value from the tip. Here, the average δ value was obtained by calculating the average indentation of 1024 points or more using 50 nm as the upper limit. The maximum load was set to a value with an average δ value of 3 nm or more for measurement. Furthermore, the distance between the maximum and minimum heights in the cantilever probe's indentation direction scan, i.e., the peak force amplitude, was set to a value within 5 times the pull-back process of the force curve for measurement.
[0558] Force curves were obtained using the Peak Force QNM (Quantitative Nanomechanical Mapping) mode. The measurement conditions using the RTESPA-300 and the RTESPA-150 are shown below.
[0559] (Literature A) Sader JE, Sanelli JA, AdamsonB.D.,Monty JP, Wei
[0560] (Reference B) ISO13095:2014
[0561] <Measurement conditions using RTESPA-300>
[0562] Cantilever: RTESPA-300 (Bruker)
[0563] Device: Dimension Icon (Bruker)
[0564] Measurement mode: Peak Force QNM
[0565] Measurement atmosphere: 24℃ / atmospheric / humidity 41%
[0566] Measurement range: 10μm × 10μm
[0567] Number of measurement points: 256 × 256 points
[0568] Cantilever movement speed: 0.2Hz
[0569] Maximum load: 40 nN
[0570] Peak Force Frequency: 1kHz
[0571] Peak Force Amplitude: 30nm
[0572] Feedback Gain: Auto
[0573] <Measurement conditions using RTESPA-150>
[0574] Cantilever: RTESPA-150 (Bruker)
[0575] Device: Dimension Icon (Bruker)
[0576] Measurement mode: Peak Force QNM
[0577] Measurement atmosphere: 24℃ / atmospheric / humidity 41%
[0578] Measurement range: 1μm × 1μm
[0579] Number of measurement points: 32×32 points
[0580] Cantilever movement speed: 0.1Hz
[0581] Maximum load: 0.5 nN
[0582] Peak Force Frequency: 1kHz
[0583] Peak Force Amplitude: 150nm
[0584] Feedback Gain: Auto
[0585]
[0586]
Claims
1. An optical laminate comprising a linear polarizer and a phase retardation layer laminate, The in-plane standard deviation σ of the visibility correction polarization degree of the linear polarizer is greater than 0.001%. The phase difference layer stack has λ / 2 and λ / 4 portions sequentially from the side closest to the linear polarizer. The λ / 2 portion has one pair of in-phase phase retardation layers and at least one thickness-direction phase retardation layer disposed between the pair of in-phase phase retardation layers. The λ / 4 section has at least one thickness-direction phase retardation layer and at least one in-plane phase retardation layer sequentially from the side closest to the linear polarizer.
2. The optical laminate according to claim 1, wherein, The linear polarizer is a cured product of dichroic pigments and polymeric liquid crystal compounds that have been oriented.
3. The optical laminate according to claim 1 or 2, wherein, The indentation elastic modulus of the linear polarizer is below 10000 MPa.
4. The optical laminate according to claim 1 or 2, wherein, The Nz coefficient at a wavelength of 550 nm in the λ / 2 section is greater than or equal to 0.6 and less than 1.
0.
5. The optical laminate according to claim 1 or 2, wherein, Viewed from the thickness direction of the optical stack, in the λ / 2 section, the angle between the slow axes of the two pairs of interphase difference layers is less than 5°.
6. The optical laminate according to claim 1 or 2, wherein, In the λ / 2 section, the sum of the thickness direction phase differences at 550 nm of the at least one thickness direction phase difference layer is -90 nm to -40 nm.
7. The optical laminate according to claim 1 or 2, wherein, In the λ / 2 section, the number of the at least one thickness-direction phase difference layer is 1.
8. The optical laminate according to claim 1 or 2, wherein, In the λ / 4 section, the sum of the thickness direction phase differences at 550 nm of the at least one thickness direction phase difference layer is -120 nm or more.
9. The optical laminate according to claim 1 or 2, wherein, Viewed from the thickness direction of the optical stack, the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion is approximately 15°, and the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion is approximately 75°, or the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 2 portion is approximately 75°, and the angle between the transmission axis of the linear polarizer and the slow axis of the λ / 4 portion is approximately 15°.
10. The optical laminate according to claim 1 or 2, wherein, The in-plane phase difference layers of the λ / 2 portion and the λ / 4 portion are polymers of polymeric liquid crystal compounds that have been oriented, and are reverse wavelength dispersive λ / 4 plates.
11. The optical laminate according to claim 1 or 2, wherein, The thickness direction phase difference layers of the λ / 2 portion and the λ / 4 portion are polymers of polymeric liquid crystal compounds that have been oriented, and are positive C-plates.
12. The optical laminate according to claim 1 or 2, wherein, In the phase difference layer stack, at least one of the in-plane phase difference layers is stacked with any of the thickness direction phase difference layers without an adhesive layer.
13. The optical laminate according to claim 1 or 2, wherein, The phase difference layer laminate also includes one or more bonding layers, which are cured layers of ultraviolet-curable adhesives.
14. An image display device comprising a reflective image display layer and an optical laminate as described in claim 1 or 2.
Citation Information
Patent Citations
Polarizing plate and its manufacturing method
JP2005208456A
Compound, optical film, and manufacturing method for optical film
JP2009173893A
Polarizer plate and method for manufacturing the same
JP2010191389A
Optical laminate and method of manufacturing the same
JP2011107686A
Polarizing plate
JP2016126345A